Laminated film
The laminated film with a resin layer composed of specific resin combinations addresses adhesion issues by ensuring uniform distribution and elastic modulus control, providing robust adhesion across temperature variations.
Patent Information
- Application Number
- CN202380040853.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-16
- Filing Date
- 2023-06-15
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-15
AI Technical Summary
Existing laminated films face issues with insufficient adhesion to functional materials like EVA, PVB, and PVA, particularly in low-temperature environments, leading to peeling and reduced performance.
A laminated film with a resin layer containing specific combinations of acrylic, polyester, and polyurethane resins, optimized to maintain adhesion across varying temperatures, ensuring uniform distribution and elastic modulus control through GCIB-TOF-SIMS normalization and AFM elastic modulus measurements.
The laminated film achieves excellent adhesion to various functional materials regardless of temperature, including low-temperature environments, by uniformly dispersing resin components and controlling elastic modulus, thereby enhancing durability and reliability.
Smart Images

Figure BDA0005136637210000101 
Figure BDA0005136637210000321 
Figure BDA0005136637210000401
Abstract
Description
Technical Field
[0001] The present invention relates to a laminated film and more particularly to a laminated film used together with a functional material such as an ethylene-vinyl acetate copolymer, polyvinyl alcohol, or polyvinyl butyral in applications such as solar cell members, laminated glass, and polarizer protection. Background Art
[0002] In many applications, research is being conducted on combining films with other components with the help of functional materials such as ethylene-vinyl acetate copolymer (hereinafter referred to as EVA), polyvinyl alcohol (hereinafter referred to as PVA), and polyvinyl butyral (hereinafter referred to as PVB). For example, in the backplane of a solar cell, EVA is provided on a laminated film to form a solar cell unit. In the use of laminated glass, PVB and EVA are inserted between two pieces of glass to form laminated glass. In addition, in the use of polarizer protective film, research is being conducted on providing films on both sides of a polarizing PVA layer as protective layers.
[0003] In particular, solar power generation is attracting attention as a semi-permanent and pollution-free next-generation energy source, so solar cells are rapidly becoming popular. In addition, in order to give window glass for automobiles and building materials functions such as heat insulation and display, laminated glass with functional films inserted is also being studied. Most of these components are used outdoors and are required to be able to be used without problems in various temperature environments, such as high temperature and high humidity in summer, or low temperature environments (below freezing point) in cold regions.
[0004] However, when the film is combined with other functional materials as described above, the adhesion of the film to the functional materials becomes a problem, and for example, for the film studied in the past, there is a problem of insufficient adhesion with EVA, PVB, PVA, etc. If these functional materials are peeled off from the film, it is difficult to be used as the final product.
[0005] To address this problem, there are methods of providing a resin layer on the film surface to optimize adhesion, a method of adding water-soluble polymers such as PVA to the resin layer to make the surface energy close to the target functional material to be bonded (Patent Document 1), a method of forming a hydrophilic easy-adhesive layer by an online coating method within the manufacturing process of a polyester film (Patent Document 2), and a method of improving the softness and moisture-heat resistance of the easy-adhesive layer (Patent Document 3), etc.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2000-336309
[0009] Patent Document 2: Japanese Patent Application Publication No. 2001-179913
[0010] Patent Document 3: Japanese Patent Application Publication No. 2011-156848 Summary of the invention
[0011] Problems to be solved by the invention
[0012] However, as in patent document 1, the method of adding water-soluble polymer in the coating film laminated on the film is a method for improving adhesion by making the surface free energy of the coating film and PVA similar, even if the adhesion with PVA having a certain specific saponification degree is good, the adhesion with other PVAs with different saponification degrees, etc., will also deteriorate, etc., and there is a problem in versatility. Moreover, since the coating film will swell or shrink according to the temperature used, there is also a problem that adhesion is reduced according to the temperature used. The method of laminating the hydrophilic easy-adhesive layer by the online coating method as in patent document 2 also has the same problem as the method of patent document 1. In addition, for the method of improving the flexibility of the easy-adhesive layer as in patent document 3, the adhesion and hardness of the easy-adhesive layer caused by temperature are large, so there is a problem that adhesion will deteriorate according to the temperature used.
[0013] Therefore, the conventional resin layers listed in Patent Documents 1 to 3 have insufficient general-purpose adhesion to various functional materials and have a problem of poor adhesion to functional materials, particularly in a low-temperature environment (below freezing point) assumed for outdoor use.
[0014] In order to solve the above problems, the present invention aims to provide a laminate film having excellent general adhesion to various functional materials and having high adhesion to functional materials regardless of the use temperature, particularly even in a low temperature environment (below freezing point).
[0015] Means of solving the problem
[0016] In view of the above problems, the inventors conducted intensive research and found that by using a laminated film provided with a resin layer having specific physical properties, a laminated film having excellent adhesion between the resin layer and the functional material provided on the resin layer can be formed, thereby completing the present invention. That is, the present invention has the following configuration.
[0017] A laminated film having a resin layer on at least one surface, characterized in that the resin layer satisfies at least one of the following characteristics A to C, and when the GCIB-TOF-SIMS positive secondary ion normalized intensity of each component at a position 20% thickness and a position 50% thickness from the surface layer of the resin layer is set to Xs and Xc, respectively, all components satisfy 0.5≤Xs / Xc≤2.0.
[0018] Feature A: Contains three types of resins: acrylic resin, polyester resin and polyurethane resin;
[0019] Feature B: Contains acrylic modified polyester resin and polyurethane resin;
[0020] Feature C: Contains three skeletons: acrylic skeleton, polyester skeleton and polyurethane skeleton.
[0021] Effects of the Invention
[0022] According to the present invention, it is possible to provide a laminate film which has excellent general-purpose adhesiveness to various functional materials and has high adhesiveness to various functional materials regardless of the use temperature, particularly even in a low temperature environment (below freezing point). DETAILED DESCRIPTION
[0023] The laminated film of the present invention will be described in detail below, but the present invention is not to be construed as being limited to the embodiments including the following examples, and various modes that can achieve the object of the invention and do not depart from the gist of the invention are of course included in the scope of the present invention.
[0024] The laminated film of the present invention has a resin layer on at least one surface. Here, the film refers to a sheet-like molded body with a thermoplastic resin as the main component, and the main component refers to a component that contains more than 50% by mass and less than 100% by mass in all the constituent components, and the same explanation can be given below. The material of the film is not particularly specified. For the thermoplastic resin used in the laminated film as described above, polyethylene, polypropylene, poly (4-methylpentene-1), chain polyolefins such as polyacetal, ring-opening metathesis polymers of norbornene, addition polymers, alicyclic polyolefins as addition copolymers with other olefins, polylactic acid, biodegradable polymers such as polybutylene succinate, polyamides such as nylon 6, nylon 11, nylon 12, nylon 66, aromatic polyamides, polymethyl methacrylate, polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol can be used. , polyvinyl butyral, ethylene vinyl acetate copolymer, polyacetal, polyglycolic acid, polystyrene, styrene copolymer polymethyl methacrylate, polycarbonate, polytrimethylene terephthalate, polyethylene terephthalate, polybutylene terephthalate, polyesters such as polyethylene 2,6-naphthalate, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polyphenylene sulfide, polyether imide, polyimide, polyarylate, tetrafluoroethylene resin, trifluoroethylene resin, trifluorochloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, etc. Among them, from the viewpoint of excellent performance such as mechanical properties, electrical properties, dimensional stability, transparency, chemical resistance, etc., polyester is particularly preferably used. They can be copolymers or mixtures of two or more resins.
[0025] A laminated film is a film formed by laminating two or more layers having different compositions. In addition, a resin layer generally refers to a primer layer provided on the surface of a film, and is a layer provided to bond the film to other members.
[0026] Polyester is a general term for polymers with ester bonds as the main bond chain. It is preferred to use a variety with at least one component selected from ethylene terephthalate, trimethylene terephthalate, 2,6-naphthalene dicarboxylic acid ethylene glycol, butylene terephthalate, 2,6-naphthalene dicarboxylic acid propylene glycol, α, β-bis (2-chlorophenoxy) ethane-4,4'-dicarboxylic acid ethylene glycol ester as the main component. Here, the main component refers to the component (structural unit) containing more than 50 mol% and less than 100 mol% when all the components (structural units) constituting the polymer are set to 100 mol%. It should be noted that the film with polyester resin as the main component is sometimes referred to as polyester film below.
[0027] In the laminated film of the present invention, it is preferred to have a resin layer on the surface of the substrate film. The type of substrate film is not particularly limited, and a polyester film is preferably used, and a polyethylene terephthalate film is more preferably used. In addition, when heat, shrinkage stress, etc. act on the laminated film, a polyethylene naphthalate film having excellent heat resistance and rigidity is preferably used. Here, polyethylene terephthalate refers to a polyester with polyethylene terephthalate as the main constituent component, and a polyethylene terephthalate film refers to a film containing polyethylene terephthalate exceeding 50% by mass and being less than 100% by mass when all the components constituting the film are set to 100% by mass. The same explanation can also be made for polyethylene naphthalate and polyethylene naphthalate film.
[0028] It should be noted that, when there are multiple components equivalent to polyethylene terephthalate in the film, if the total amount thereof exceeds 50% by mass and is 100% by mass or less, the film is regarded as a polyethylene terephthalate film. In this regard, the same explanation can be given to polyethylene naphthalate films.
[0029] In addition, the polyester film for substrate is preferably a biaxially oriented polyester film. The so-called biaxially oriented polyester film refers to a polyester film showing a biaxially oriented pattern in wide-angle X-ray diffraction. For the biaxially oriented polyester film, it can usually be obtained by stretching the polyester sheet or film in an unstretched state in two orthogonal directions (for example, the length direction and the width direction), and terminating the crystal orientation by heat treatment. The stretching ratio at this time is preferably 2.5 times or more and 5.0 times or less. By making the polyester film for substrate a biaxially oriented polyester film, the thermal stability of the laminated film, especially the dimensional stability and mechanical strength are improved, and the planarity is also improved. It should be noted that the length direction refers to the direction in which the film travels in the manufacturing process, and in the state of the film roll, it is equivalent to the winding direction. The width direction refers to the direction orthogonal to the length direction within the film surface.
[0030] Furthermore, various additives may be added to the polyester film for substrate to such an extent that the properties thereof are not deteriorated, such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic microparticles, fillers, antistatic agents, nucleating agents, etc. It should be noted that these components may also be used in combination of multiple types.
[0031] The thickness of the polyester film for substrate is not particularly limited and can be appropriately selected according to the application and type. From the viewpoints of mechanical strength, operability, etc., it is usually preferably 10 to 500 μm, more preferably 20 to 250 μm, and most preferably 30 to 150 μm. In addition, the polyester film for substrate can be a composite film obtained by coextrusion, or a film formed by laminating films obtained by various methods.
[0032] From the viewpoint of improving the general-purpose adhesiveness in a normal temperature environment and the adhesiveness in a low temperature environment, the resin layer in the laminated film of the present invention satisfies at least one of the characteristics A to C.
[0033] Feature A: Contains three types of resins: acrylic resin, polyester resin, and polyurethane resin.
[0034] Feature B: Contains acrylic modified polyester resin and polyurethane resin.
[0035] Feature C: Contains three skeletons: acrylic skeleton, polyester skeleton and polyurethane skeleton.
[0036] In addition, from the above viewpoints, for the laminated film, when the normalized intensities of positive secondary ions of GCIB-TOF-SIMS of each component at a position of 20% thickness and 50% thickness from the surface of the resin layer are set to Xs and Xc, respectively, all components satisfy 0.5≤Xs / Xc≤2.0. Furthermore, from the above viewpoints, for the laminated film of the present invention, when the normalized intensities of positive secondary ions of GCIB-TOF-SIMS of each component at a position of 80% thickness from the surface of the resin layer is set to Xb, it is preferred that all components satisfy 0.5≤Xb / Xc≤2.0.
[0037] It should be noted that, here, GCIB is the abbreviation of gas cluster ion beam, and TOF-SIMS is the abbreviation of time-of-flight secondary ion mass spectrometry. In the analysis using GCIB-TOF-SIMS, in the embodiment of feature A, ions derived from acrylic resin, polyester resin, and polyurethane resin are generated, and in the embodiment of feature C, ions derived from acrylic skeleton, polyester skeleton, and polyurethane skeleton are generated. In addition, in the embodiment (the embodiment that satisfies feature B) that includes acrylic modified polyester resin as a substitute for acrylic resin and polyester resin, ions derived from acrylic acid and polyester are also generated. Therefore, all components here refer to acrylic components, polyester components, and polyurethane components, which are detected in the form of ions in the analysis using GCIB-TOF-SIMS. It should be noted that, as described above, in the case of satisfying any of the embodiments of features A to C, ions derived from acrylic acid, polyester, and polyurethane are generated, so in any embodiment, the same interpretation can be made for "all components".
[0038] From the perspective of universal adhesion with various functional materials, the resin layer in the laminated film of the present invention needs to satisfy at least one of the characteristics A to C. The functional material mentioned here refers to a layer disposed on the resin layer in the laminated film, and refers to a layer having functions such as sealing, adhesion, design, durability, weather resistance, and impact resistance. For example, a solar cell is usually constructed by laminating a power generation element (solar cell unit), a transparent substrate such as glass, and a resin sheet called a backplane (back protection sheet), but when these components are laminated, a "sealing material" having functions such as protecting the solar cell unit from external environmental influences such as water intrusion and having adhesion to the backplane is sometimes used as a functional material. In addition, when the laminated film is laminated to glass or inserted between two sheets of glass and used as a glass structure, an "intermediate layer" having functions such as bonding the glass to the laminated film and improving the design, durability, weather resistance, and impact resistance of the laminated glass is sometimes used as a functional material. The sealing material and the intermediate layer as the functional material are not particularly limited, and examples thereof include EVA, PVB, and PVA, and the details thereof will be described later.
[0039] By making the resin layer contain polyurethane resin or polyurethane skeleton, hydrogen bonds can be formed with hydroxyl groups of EVA, PVB, PVA, etc., and high adhesion can be exhibited. By making the resin layer contain polyester resin or polyester skeleton, high adhesion with functional materials such as EVA, PVB, PVA can be achieved through hydrogen bonds with hydroxyl groups, and in the case where the substrate is a polyester film, good adhesion to the substrate can also be achieved. By making the resin layer contain acrylic resin or acrylic skeleton, in addition to promoting the curing of the resin layer when the resin layer is formed by coating, it is also easy to make the water drop contact angle of the resin layer described later to be more than 65° and less than 90°.
[0040] It should be noted that in the laminated film of the present invention, when the acrylic resin and the polyester resin are acrylic-modified polyester resins (in other words, when acrylic-modified polyester resins are included as substitutes for polyester resins and acrylic resins), the same effect as a laminated film comprising polyester resins and acrylic resins, or a laminated film comprising a polyester skeleton and an acrylic skeleton can be obtained.
[0041] The resin layer in the laminated film of the present invention may also contain polyester resin and polyurethane resin in the form of polyester-polyurethane copolymer. The layer containing acrylic resin and polyester-polyurethane copolymer can be regarded as "a layer containing three resins of acrylic resin, polyester resin and polyurethane resin" and "a layer containing three skeletons of acrylic skeleton, polyester skeleton and polyurethane skeleton", that is, a layer satisfying both characteristics A and C, and the layer containing acrylic modified polyester resin and polyester-polyurethane copolymer can be regarded as "a layer containing acrylic modified polyester resin and polyurethane resin" and "a layer containing three skeletons of acrylic skeleton, polyester skeleton and polyurethane skeleton", that is, a layer satisfying both characteristics B and C.
[0042] In addition, generally speaking, functional materials such as EVA, PVB, PVA have a wide range of elastic moduli depending on the degree of saponification. In addition, even if these functional materials have a low elastic modulus and are relatively soft at room temperature, for example, the elastic modulus will increase at a low temperature of -20°C, and the difference in elastic modulus with that at room temperature will become larger. Therefore, even if the above-mentioned functional materials are fully bonded to the resin layer at room temperature, it is easy to peel off at the interface between the above-mentioned functional materials and the resin layer at a low temperature. In the adhesion between the above-mentioned functional materials and the resin layer having such a wide range of elastic moduli, the elastic modulus of the resin layer is important. It is known that the larger the elastic modulus of the resin layer (i.e., the harder), the worse the adhesion. On the other hand, usually, the elastic modulus of the resin layer will increase in the same way as the elastic modulus of the above-mentioned functional materials increases at a low temperature of -20°C.
[0043] When controlling the elastic modulus of the resin layer, it is important to mix resins with different elastic moduli. Generally, acrylic resins, polyester resins, polyurethane resins, acrylic modified polyester resins, and polyester-polyurethane copolymers each have different elastic moduli. More specifically, generally polyester resins have a high elastic modulus, polyurethane resins have a low elastic modulus, and acrylic resins have an elastic modulus between them. Therefore, by mixing these three resins, the elastic modulus can be easily controlled. However, in the case of polyurethane resins, for example, in aliphatic polyurethane resins containing aliphatics in a part of the composition and aromatic polyurethane resins containing aromatics in a part of the composition, the rigidity of the aromatic chain causes the elastic modulus of the aromatic polyurethane resin to become higher, and the elastic modulus is different depending on the skeleton constituting each resin. Therefore, the elastic modulus of polyester resins, acrylic resins, and polyurethane resins is sometimes not necessarily in the order described above. In addition, acrylic modified polyester resins have the characteristics of acrylic resins and polyester resins, and polyester-polyurethane copolymers have the characteristics of polyester resins and polyurethane resins, and therefore generally have elastic moduli between the two.
[0044] As described above, from the perspective of improving general adhesion and adhesion under low temperature environment, the resin layer needs to satisfy at least one of the characteristics A to C. On the other hand, for acrylic resin, polyester resin and polyurethane resin, on its skeleton, acrylic resin is hydrophobic, and there are different aspects of hydrophilicity and properties in the order of polyester resin and polyurethane resin. Generally, it is known that when a hydrophobic resin and a hydrophilic resin are mixed to form a resin layer, each resin with its own properties is distributed in the depth direction. Therefore, when these three resins are simply mixed, for example, there is more acrylic resin on the surface side of the resin layer, and more polyester resin and polyurethane resin on the inner side, so that a deviation in the distribution of components is generated in the resin layer. The deviation of the distribution of components can also occur between acrylic modified polyester resin and polyurethane resin, and between acrylic modified polyester resin and polyester-polyurethane copolymer.
[0045] Therefore, the inventors conducted in-depth research and found that on the basis of making the resin layer satisfy at least one of the characteristics A to C, when the GCIB-TOF-SIMS normalized positive secondary ion intensity of each component at a position of 20% thickness and 50% thickness from the surface of the resin layer is set to Xs and Xc, respectively, all components satisfy 0.5≤Xs / Xc≤2.0, thereby having excellent flexibility under normal temperature environment, and suppressing the increase of elastic modulus under low temperature environment, and being able to show excellent adhesion under any environment. Furthermore, the laminated film of the present invention is also preferably set to Xb, when the GCIB-TOF-SIMS normalized positive secondary ion intensity of each component at a position of 80% thickness from the surface of the resin layer is set to Xb, all components satisfy 0.5≤Xb / Xc≤2.0.
[0046] The laminated film of the present invention satisfies 0.5≤Xs / Xc≤2.0, which means that each component is uniformly dispersed from the vicinity of the surface of the resin layer to the central portion, and satisfies 0.5≤Xb / Xc≤2.0, which means that each component is uniformly dispersed from the central portion of the resin layer to the vicinity of other layers (for example, a layer formed by a substrate film). That is, when both Xs / Xc and Xb / Xc are within the above range, it means that each component is uniformly dispersed in the thickness (depth) direction of the resin layer. On the contrary, when Xs / Xc and Xb / Xc do not satisfy the above range, it means that there is an uneven dispersion of each component in the depth direction of the resin layer.
[0047] When the resin layer satisfies 0.5≤Xs / Xc≤2.0 in all components, it contributes greatly to the adhesion with the functional material, so it is particularly important. Furthermore, when the resin layer also satisfies 0.5≤Xb / Xc≤2.0 in all components, the resin layer is uniform as a whole, it is easy to obtain sufficient adhesion under normal temperature environment, and the decrease in adhesion under low temperature can be further reduced, so it is preferred.
[0048] Xs, Xc, and Xb of the resin layer can be measured by GCIB-TOF-SIMS, and the specific measurement method and conditions are described below. In addition, "the position at 20% thickness from the surface of the resin layer" means the position at 20% when the surface of the resin layer is set to 0% and the interface between the resin layer and other layers is set to 100%. The same explanation can be given to "the position at 50% thickness from the surface of the resin layer" and "the position at 80% thickness from the surface of the resin layer".
[0049] The laminated film of the present invention preferably contains a compound that satisfies at least one of the characteristics A to C and has both hydrophobic and hydrophilic properties. By setting it in this way, the distribution deviation of each component in the depth direction can be suppressed, and a more uniform resin layer can be formed. By making each component more uniformly dispersed in the thickness direction, the elastic modulus of the entire resin layer becomes more uniform, the universal adhesion with various functional materials is improved, and high adhesion can be achieved even in a low temperature environment.
[0050] In addition, the laminated film of the present invention preferably has at least one of the following features 1 and 2, when the AFM elastic modulus of the resin layer measured by an atomic force microscope (AFM) at a temperature T°C is set as P(T), P(-20)-P(25) is set as ΔP, and P(-20) / P(25) is set as the elastic modulus ratio P':
[0051] Feature 1: ΔP is 0.2 GPa or more and 2.0 GPa or less.
[0052] Feature 2: The elastic modulus ratio P' is 0.1 or more and 2.3 or less.
[0053] The AFM elastic modulus of the resin layer can be measured using a known measuring device, such as NanoScope V manufactured by Bruker Ecos Co., Ltd. The measuring method and steps when using the device are described below. P(-20) is the AFM elastic modulus at -20°C, which represents the AFM elastic modulus in a low temperature environment assumed to be used in cold areas and desert areas. On the other hand, P(25) is 25°C, i.e., the AFM elastic modulus in a room temperature environment. In general, it is known that functional materials such as EVA, PVB, and PVA increase their elastic modulus in a low temperature environment of -20°C. The larger the elastic modulus of the functional material, the worse the adhesion between the resin layer and the functional material as the adherend. Therefore, even if the functional materials such as EVA, PVB, and PVA are fully bonded to the resin layer at room temperature, there is a tendency for peeling to easily occur at the interface between the functional material and the resin layer in a low temperature environment.
[0054] In the case where the laminated film of the present invention does not have feature 2, by making ΔP above 0.2 GPa, the state change of the resin layer caused by temperature during the thermal processing step with the functional material becomes sufficient, and the adhesion between the laminated film and the functional material is improved. In addition, if the laminated film of the present invention does not have feature 2 and ΔP is below 2.0, the increase in the elastic modulus at -20°C is suppressed, and the reduction in adhesion to the functional material caused by over-curing of the resin layer is reduced. From the above viewpoints, the more preferred range of ΔP is above 0.3 GPa and below 1.7 GPa, and further preferably above 0.4 GPa and below 1.3 GPa. In the prior art described in Patent Documents 1 to 3, even if the adhesion at 25°C is sufficient, there is a situation where the elastic modulus of the adhesive layer changes when it is set to -20°C and sufficient adhesion cannot be maintained.
[0055] In the case where the laminated film of the present invention does not have feature 1, by making the elastic modulus ratio P' to be 0.1 or more, the increase in elastic modulus at -20°C can be suppressed, and the reduction in adhesion to the functional material caused by over-curing of the resin layer can be reduced. In addition, by making the laminated film of the present invention not have feature 1, and the elastic modulus ratio P' is 2.3 or less, the state change of the resin layer due to temperature during the thermal processing step with the functional material becomes sufficient, and the adhesion between the laminated film and the functional material is improved. In addition, for the substrate film that is usually a sheet-shaped molded body with a thermoplastic resin as the main component, the elastic modulus becomes higher than 25°C by cooling to -20°C, or forms a close value before and after cooling, so the preferred range of the elastic modulus ratio P' is 0.9 or more and 2.1 or less, and more preferably 1.1 or more and 2.0 or less. By making the elastic modulus ratio P' in the above range, there is a tendency to further suppress the reduction in adhesion to the functional material in a low temperature environment.
[0056] It should be noted that from the viewpoint of improving the adhesion of the resin layer to the functional material under low temperature environment, the laminated film of the present invention only needs to have at least one of the features 1 and 2, and more preferably has both the features 1 and 2. By having both the features 1 and 2, it is not only easy to reduce the reduction in adhesion to the functional material under low temperature environment, but also easy to make the adhesion to the functional material under normal temperature environment sufficient. As a method of having at least one of the above-mentioned features 1 and 2, or reaching the above-mentioned preferred ranges respectively, there can be cited, for example, a method of adjusting the glass transition temperature of the resin layer. More specifically, by making the glass transition temperature of the resin layer above 30°C, it is easy to reduce ΔP or adjust the elastic modulus ratio P' to the preferred range. In addition, by making the resin layer A contain an oxazoline compound or a chemical structure derived from an oxazoline compound, it is also easy to reduce ΔP or adjust the elastic modulus ratio P' to the preferred range.
[0057] In addition, in the laminated film of the present invention, P(25) is preferably 0.2 GPa or more and 1.5 GPa or less. By setting it as such a scheme, the adhesion between the resin layer A of the laminated film of the present invention and the functional material with high flexibility can be improved. From the above viewpoints, P(25) is more preferably 0.2 GPa or more and 1.3 GPa or less, and further preferably 0.3 GPa or more and 0.9 GPa or less. By making P(25) less than 1.5 GPa, the resin layer is sufficiently soft and can ensure adhesion with the functional material with high flexibility. By making P(25) more than 0.2 GPa, the resin layer will not become too soft, and the adhesion when the film is rolled up in a roll can be reduced.
[0058] As a method for making P(25) be 0.2GPa or more and 1.5GPa or the above preferred range, there is no particular limitation, for example, a method for adjusting the glass transition temperature of the resin layer can be cited. Alternatively, a method for making the polyurethane resin contained in the resin composition forming the resin layer satisfying the characteristics A and B be an aliphatic polyurethane resin or a resin formed by polymerizing an aliphatic polyisocyanate compound and a polyol compound can be cited. Moreover, when the resin composition is set to 100% by mass, it is easy to make the content of the polyurethane resin be 4% by mass or more and 60% by mass or less, preferably 4% by mass or more and 50% by mass or less. It should be noted that, with respect to the above viewpoints, in the case of having a resin layer satisfying the characteristic C, the polyurethane resin can be replaced by a polyurethane skeleton and the same explanation can be made. In addition, when a polyester-polyurethane copolymer is used as the polyurethane resin, the amount of the polyisocyanate compound added during copolymerization is used as the content of the polyurethane resin.
[0059] In the laminated film of the present invention, the glass transition temperature (hereinafter also referred to as Tg) of the resin layer is preferably above 30°C and below 80°C. By setting the Tg of the resin layer to be above 30°C, the increase in ΔP can be suppressed, and by setting the Tg of the resin layer to be below 80°C, the adhesion to the functional material can be sufficient regardless of the temperature environment and type. From the above viewpoints, the Tg of the resin layer is more preferably above 30°C and below 70°C, and further preferably above 30°C and below 55°C. It should be noted that the glass transition temperature of the resin layer can be measured using a differential scanning calorimeter (DSC), and the conditions and other details are described in the following examples.
[0060] The glass transition temperature can be adjusted by adjusting the components contained in the resin layer. In addition, when the resin layer satisfies feature B, the glass transition temperature of the resin layer can also be adjusted by adjusting the ratio of the acrylic resin component (acrylic unit) to the polyester resin component (polyester unit) in the acrylic modified polyester resin.
[0061] In the laminated film of the present invention, the water drop contact angle of the resin layer is preferably 65° or more and 90° or less. By setting such a scheme, the difference in hydrophilicity between the resin layer and the functional material becomes smaller, so the adhesion between the two can be improved. From the above viewpoints, the water drop contact angle of the resin layer is more preferably 65° or more and 85° or less, and further preferably 65° or more and 80° or less. The water drop contact angle mentioned in the present invention is obtained by the static drop method described in JIS R3257:1999. More specifically, it is a value that can be obtained by the following formula when a water drop is placed on the surface of the resin layer and reaches equilibrium in the atmosphere, which is usually used as an indicator for judging the coating property of the solid surface. That is, the smaller the value of the water drop contact angle, the better the coating property of the above-mentioned solid surface, and the larger the value, the worse the coating property. The following formula is called "Young's formula", in which the angle formed by the liquid surface and the solid surface is defined as "contact angle". It should be noted that the specific method for measuring the water drop contact angle is as described later.
[0062] γS=γLcosθ+γSL
[0063] In the above formula, γS represents the surface tension of the solid, γL represents the surface tension of the liquid, γSL represents the interfacial tension of the solid / liquid, and θ represents the contact angle.
[0064] There is no particular limitation on the method for making the water drop contact angle of the resin layer more than 65° and less than 90° or the above-mentioned preferred range, and methods for adjusting the ratio of the highly hydrophobic components and the skeleton in the resin layer can be cited. For example, by increasing the ratio of acrylic resin (an embodiment that satisfies feature A), the ratio of acrylic skeleton (an embodiment that satisfies feature C), and the ratio of acrylic modified polyester resin (an embodiment that satisfies feature B), the water drop contact angle of the resin layer can be increased. In the embodiment that satisfies feature B, the water drop contact angle of the resin layer can also be increased by increasing the ratio of acrylic resin component (acrylic unit) in acrylic modified polyester resin. In addition, as another method, a method for increasing the water drop contact angle of the resin layer by adding an oxazoline compound to the resin layer can also be used. It should be noted that these methods can be appropriately used in combination.
[0065] In the case where the resin layer satisfies at least one of the features A and B, the polyurethane resin contained in the resin layer is preferably an aliphatic polyurethane resin, and more preferably an alicyclic polyurethane resin. Here, an aliphatic polyurethane resin refers to a polyurethane resin having an aliphatic chain, and an alicyclic polyurethane resin refers to an aliphatic polyurethane resin in which a part of the aliphatic chain contains a cyclic structure. The glass transition temperature of the alicyclic polyurethane resin is also relatively high among the aliphatic polyurethane resins, so the resin layer containing the alicyclic polyurethane resin will not be softened or melted by the heat applied during the thermal processing process such as the interlayer vitrification and when used under a high temperature and high humidity environment. In addition, the occurrence of oligomers in the polyester film seeping out to the surface of the resin layer is also suppressed. Therefore, if the resin layer contains an alicyclic polyurethane resin, a resin layer with excellent adhesion, especially in a humid and heat-resistant environment, can be obtained. It should be noted that, with respect to the above aspects, in the embodiment in which the resin layer satisfies the feature C, the polyurethane resin can be replaced with a polyurethane skeleton and the same explanation can be made.
[0066] On the other hand, when the resin layer satisfies at least one of the characteristics A and B, when an aromatic polyurethane resin containing aromatic groups is used in part of its composition to replace an aliphatic polyurethane resin, for a resin composition having an aromatic polyurethane resin, the influence of the aromatic chain causes the resin layer to become rigid, and therefore cannot follow the expansion and contraction of EVA and PVB, and sometimes cannot obtain sufficient adhesion. In addition, when the resin layer is exposed to light, problems such as yellowing and embrittlement of the resin layer may sometimes occur. For example, when used for heat ray blocking glass and window glass, the quality may sometimes be reduced due to the influence of external light. It should be noted that, with respect to the above aspects, in an embodiment in which the resin layer satisfies the characteristic C, the polyurethane resin may be replaced with a polyurethane skeleton and the same explanation may be given.
[0067] The acrylic modified polyester resin that can be used in the laminated film of the present invention (the embodiment that satisfies feature B) is formed by mutually bonding an acrylic resin component and a polyester resin component, and includes, for example, a graft polymerization type and a block copolymerization type. In addition, the copolymerization ratio of the acrylic resin component and the polyester resin component in the acrylic modified polyester resin can be relatively high. For the acrylic modified polyester resin, for example, it can be manufactured by polymerizing an acrylic monomer by adding a free radical initiator to both ends of the polyester, polymerizing an acrylic monomer by adding a free radical initiator to the side chain of the polyester, or adding a hydroxyl group to the side chain of the acrylic resin to react with a polyester having an isocyanate group or a carboxyl group at the end. As described above, from the perspective of the stability of the resin layer, it is preferred that the acrylic resin component and the polyester resin component are bonded to each other.
[0068] If the acrylic resin component in the acrylic modified polyester resin increases, the water drop contact angle of the resin layer can be increased, and if the acrylic resin component decreases, the water drop contact angle of the resin layer can be reduced. In order to set the water drop contact angle of the resin layer to the range of 65° or more and 90° or less described later, the mass ratio of the acrylic resin to the polyester resin (the content of the acrylic resin [parts by mass] / the content of the polyester resin [parts by mass]), or the mass ratio of the acrylic resin component to the polyester resin component in the acrylic modified polyester resin (the content of the acrylic resin component [parts by mass] / the content of the polyester resin component [parts by mass]) can be set to 15 / 85 or more and 85 / 15 or less.
[0069] When a polyester film is used as the substrate of the laminated film of the present invention, the polyester resin component of the acrylic modified polyester resin can make the resin layer have good adhesion to the polyester film as the substrate. In addition, as a method for making the water drop contact angle of the resin layer 65° or more and 90° or less, a method for making the oxazoline compound 30 mass parts or more and 90 mass parts or less when the total amount of acrylic resin, polyester resin, polyurethane resin (or acrylic modified polyester resin and polyurethane resin) is 100 mass parts can also be used.
[0070] In addition, the resin layer preferably has at least one structure of the following formulas (1) to (5), and the acrylic modified polyester resin preferably has at least one structure of the formulas (1) to (5). The formulas (1) to (5) are polar groups that form hydrogen bonds with the hydroxyl groups of the functional materials. Therefore, by setting such a scheme, the resin layer can also form hydrogen bonds with EVA, PVB, and PVA at the sites of the formulas (1) to (5), which can improve the adhesion to the functional materials.
[0071]
[0072] The acrylic resin component constituting the acrylic modified polyester resin is preferably a resin obtained by polymerizing a hydrophilic free radical polymerizable vinyl monomer on the main chain of an acrylic resin composed of an alkyl methacrylate and / or an alkyl acrylate. By including the hydrophilic free radical polymerizable vinyl monomer in the acrylic resin component, at least one structure of the above formulas (1) to (5) can be imparted to the acrylic modified polyester.
[0073] When the total amount of the acrylic resin component is 100 parts by mass, the hydrophilic free radical polymerizable vinyl monomer is preferably 20 parts by mass or more and 50 parts by mass or less. By making the hydrophilic free radical polymerizable vinyl monomer 20 parts by mass or more and 50 parts by mass or less, it is easy to make the water drop contact angle in the range of 65° or more and 90° or less, and the adhesion to the functional material can be effectively improved.
[0074] As the acrylic resin component, alkyl methacrylate and / or alkyl acrylate can be used, and specifically, methacrylic acid, methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-hexyl methacrylate, lauryl methacrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylic acid, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, n-hexyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, etc. are preferably used. One or more of these can be used.
[0075] As for the hydrophilic free radical polymerizable vinyl monomer, specifically, as the monomer forming the structure of the above formula (1), hydroxy acrylates such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate can be listed. As the monomer forming the structure of the above formula (2), glycol esters such as ethylene glycol acrylate, ethylene glycol methacrylate, polyethylene glycol acrylate, and polyethylene glycol methacrylate can be listed. As the monomer forming the structure of the above formula (3), acrylamide compounds such as acrylamide, methacrylamide, N-hydroxymethyl acrylamide, and methoxymethyl acrylamide can be listed. As the monomer forming the structure of formula (4), cationic monomers such as aminoalkyl acrylate, aminoalkyl methacrylate, and quaternary ammonium salts thereof can be listed. As the monomer forming the structure of formula (5), glycidyl acrylate compounds such as glycidyl acrylate and glycidyl methacrylate, and unsaturated acids such as acrylic acid, methacrylic acid, maleic anhydride, itaconic acid, crotonic acid, and salts thereof can be listed. The hydrophilic radical polymerizable monomers may be used alone or in combination of two or more. Furthermore, other copolymerizable vinyl monomers may be used in combination with these hydrophilic monomers.
[0076] Examples of other copolymerizable vinyl monomers include vinyl esters such as vinyl acetate and vinyl propionate, vinyl halides such as vinyl chloride and vinyl bromide, unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, butyl acrylate, methyl methacrylate, ethyl methacrylate, and butyl methacrylate, vinyl silanes such as dimethylvinylmethoxysilane and γ-methacryloxypropyltrimethoxysilane, olefins such as ethylene, propylene, styrene, and butadiene, and diene compounds.
[0077] The polyester resin component constituting the acrylic modified polyester resin has an ester bond in the main chain or the side chain, and is composed of a dicarboxylic acid component and a diol component. As the carboxylic acid component constituting the polyester resin, aromatic, aliphatic, alicyclic dicarboxylic acids, and polycarboxylic acids with a valence of 3 or more can be used. As aromatic dicarboxylic acids, terephthalic acid, isophthalic acid, phthalic acid, phthalic acid, 2,5-dimethylterephthalic acid, sodium 5-sulfoisophthalic acid, 1,4-naphthalene dicarboxylic acid, etc., and their ester-forming derivatives can be used.
[0078] As the diol component of the polyester resin, ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, etc. can be used.
[0079] When the polyester resin component is dissolved or dispersed in an aqueous solvent to be used as an aqueous resin composition, it is preferred to copolymerize a compound containing a sulfonate group or a compound containing a carboxylate group in order to facilitate water solubility or water dispersion of the polyester resin component.
[0080] Examples of compounds containing a carboxylate group include, but are not limited to, alkali metal salts, alkaline earth metal salts, and ammonium salts of trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromellitic anhydride, 4-methylcyclohexene-1,2,3-tricarboxylic acid, trimesic acid, 1,2,3,4-butanetetracarboxylic acid, and 1,2,3,4-pentanetetracarboxylic acid.
[0081] As the compound containing a sulfonate group, for example, alkali metal salts, alkaline earth metal salts, and ammonium salts such as sulfoterephthalic acid, 5-sulfoisophthalic acid, sodium 5-sulfoisophthalate, and 4-sulfoisophthalic acid can be used, but the present invention is not limited thereto.
[0082] The acrylic modified polyester resin used in the resin composition forming the resin layer of the present invention can be produced, for example, by the following production method. First, the polyester resin component is produced as follows. For example, it can be produced by a method of directly subjecting a dicarboxylic acid component and a diol component to an esterification reaction, a method of subjecting a dicarboxylic acid component and a diol component to a first-stage process of transesterification reaction and subjecting the first-stage reaction product to a second-stage process of polycondensation reaction, etc. At this time, as a reaction catalyst, for example, alkali metals, alkaline earth metals, manganese, cobalt, zinc, antimony, germanium, titanium compounds, etc. can be used.
[0083] Next, the polyester resin component is dispersed in a solvent, and as a means of dispersing in an aqueous solvent, the polyester resin is dissolved or dispersed in an aqueous solution of an alkaline compound such as ammonia water, sodium hydroxide, potassium hydroxide, or various amines under stirring. In this case, a water-soluble organic solvent such as methanol, ethanol, isopropyl alcohol, butyl cellosolve, or ethyl cellosolve may be used in combination.
[0084] Next, in order to produce an acrylic modified polyester resin, a polymerization initiator and, if necessary, an emulsifying dispersant are added to the dispersion of the polyester resin component, and the acrylic resin component is slowly added while the temperature is kept constant, and then the mixture is reacted for several hours to produce a dispersion of the acrylic modified polyester. The obtained dispersion is a mixture of the acrylic modified polyester resin component, the polyester resin component, and the acrylic resin component.
[0085] The polymerization initiator is not particularly limited, and a common radical polymerization initiator can be used, for example, water-soluble peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide, oil-soluble peroxides such as benzoyl peroxide and tert-butyl hydroperoxide, or azo compounds such as azobisisobutyronitrile.
[0086] When the resin layer satisfies at least one of the characteristics A and B, the polyurethane resin contained in the resin composition forming the resin layer in the laminated film of the present invention is preferably an aliphatic polyurethane resin. In addition, the polyurethane resin used in the present invention is not particularly limited, and is preferably a polyurethane resin formed by polymerizing an aliphatic polyisocyanate compound and a polyol compound. It should be noted that when the resin layer satisfies the characteristic C, it is preferred to have a skeleton that is preferably possessed by a polyurethane resin when the resin layer satisfies at least one of the characteristics A and B.
[0087] First, the aliphatic polyisocyanate compound used in the resin composition is described. As the aliphatic polyisocyanate compound preferably used in the resin composition, it is preferred that there are aliphatic polyisocyanate compounds with multiple isocyanate groups in the molecule, for example, 1,6-hexane diisocyanate, isophorone diisocyanate, methylene bis (4-cyclohexyl isocyanate), 2,2,4-trimethyl hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, bis (2-isocyanatoethyl) fumarate, bis (4-isocyanatocyclohexyl) methane, dicyclohexylmethane 4,4-diisocyanate lysine diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated phenylmethane diisocyanate, etc. can be listed. It should be noted that the aliphatic polyisocyanate compound used in the present invention can be one kind, or it can be more than two kinds.
[0088] In the present invention, any of the aforementioned aliphatic polyisocyanate compounds can be suitably used, wherein alicyclic polyisocyanate compounds are preferably used. The aliphatic polyurethane resin polymerized by the alicyclic polyisocyanate compound has a high glass transition temperature among aliphatic polyurethane resins. Therefore, for the heat imparted during lamination of functional materials or under high temperature and high humidity environments, it will not soften or melt in the resin layer, nor will it seep out to the surface of the resin layer, and can exist in the resin layer without change. Therefore, the adhesion between the resin layer and the functional material can be maintained, especially in the evaluation of moisture-heat resistant bonding.
[0089] Next, the polyol compound used in the resin composition is described. For the polyol compound used in the resin composition, there is no particular restriction as long as it has multiple hydroxyls. As such a polyol compound, for example, aromatic polyether polyols, aliphatic polyether polyols, polyester polyols, polycarbonate polyols and polycaprolactone polyols can be cited. Hereinafter, for these polyol compounds, their specific examples are described in sequence.
[0090] Examples of the aromatic polyether polyol include ethylene oxide addition diols of bisphenol A, propylene oxide addition diols of bisphenol A, butylene oxide addition diols of bisphenol A, ethylene oxide addition diols of bisphenol F, propylene oxide addition diols of bisphenol F, propylene oxide addition diols of bisphenol F, alkylene oxide addition diols of hydroquinone, and alkylene oxide addition diols of naphthoquinone.
[0091] Examples of the aliphatic polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, 1,2-polybutylene glycol, polyisobutylene glycol, copolymer polyols of propylene oxide and tetrahydrofuran, copolymer polyols of ethylene oxide and tetrahydrofuran, copolymer polyols of ethylene oxide and propylene oxide, copolymer polyols of tetrahydrofuran and 3-methyltetrahydrofuran, copolymer polyols of ethylene oxide and 1,2-butylene oxide, and copolymer polyols of tetrahydrofuran and 3-methyltetrahydrofuran. Examples of the alicyclic polyether polyol include ethylene oxide addition diols of hydrogenated bisphenol A, propylene oxide addition diols of hydrogenated bisphenol A, butylene oxide addition diols of hydrogenated bisphenol A, ethylene oxide addition diols of hydrogenated bisphenol F, propylene oxide addition diols of hydrogenated bisphenol F, butylene oxide addition diols of hydrogenated bisphenol F, dimethylol compounds of dicyclopentadiene, and tricyclodecanedimethanol.
[0092] Examples of the polyester polyol include polyester polyols obtained by reacting a polyol such as ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, tetramethylene glycol, polytetramethylene glycol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 1,9-nonanediol, and 2-methyl-1,8-octanediol with a polybasic acid such as phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, adipic acid, and sebacic acid.
[0093] Examples of the polycarbonate polyol include 1,6-hexane polycarbonate.
[0094] Examples of the polycaprolactone polyol include polycaprolactone diols obtained by reacting ε-caprolactone with a divalent diol such as ethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, tetramethylene glycol, polytetramethylene glycol, 1,2-polybutylene glycol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, and 1,4-butanediol.
[0095] In addition, examples of the polyol compound that can be used for the resin composition include ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, poly-β-methyl-δ-valerolactone, hydroxy-terminated polybutadiene, hydroxy-terminated hydrogenated polybutadiene, castor oil-modified polyol, terminal diol compounds of polydimethylsiloxane, polydimethylsiloxane carbitol-modified polyol, and the like.
[0096] In the resin composition, any of these polyol compounds can be preferably used, wherein aliphatic polyether polyols are preferably used. By using aliphatic polyether polyols, aliphatic polyurethane resins can be made soft, so it is easier to make the above-mentioned P(25) be more than 0.2 GPa and less than 1.5 GPa, which can improve the general adhesion to EVA, PVB, and PVA at room temperature. It should be noted that the polyol compound used in the resin composition can be one kind or two or more kinds.
[0097] From the above viewpoints, the specific structure of the polyurethane resin used in the resin composition is particularly preferably composed of the following aliphatic polyisocyanate compounds and aliphatic polyether polyols. Examples of the aliphatic polyisocyanate compound include 1,6-hexane diisocyanate, isophorone diisocyanate, methylenebis(4-cyclohexyl isocyanate), 2,2,4-trimethylhexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, bis(2-isocyanateethyl)fumarate, bis(4-isocyanatecyclohexyl)methane, dicyclohexylmethane 4,4-diisocyanatelysine diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated phenylmethane diisocyanate.
[0098] Examples of the aliphatic polyether polyol include polyethylene glycol, polypropylene glycol, polytetramethylene glycol, 1,2-polybutylene glycol, and polyisobutylene glycol.
[0099] The aliphatic polyurethane resin used in the resin composition is obtained by dissolving or dispersing a chain extender in water in addition to an aliphatic polyisocyanate compound and a polyol compound as needed, and polymerizing the mixture by a known method.
[0100] Examples of the chain extender include polyols such as ethylene glycol, 1,4-butanediol, trimethylolpropane, triisopropanolamine, N,N-bis(2-hydroxypropyl)aniline, hydroquinone-bis(β-hydroxyethyl)ether, and resorcinol-bis(β-hydroxyethyl)ether; polyamines such as ethylenediamine, propylenediamine, hexamethylenediamine, phenylenediamine, toluenediamine, diphenyldiamine, diaminodiphenylmethane, diaminodiphenylmethane, diaminodicyclohexylmethane, piperazine, isophoronediamine, diethylenetriamine, and dipropylenetriamine; hydrazines; and water.
[0101] The content of the polyurethane resin in the resin composition is not particularly limited as long as it is a range that can show the general adhesion and moisture-heat-resistant adhesion of the polyurethane resin to EVA, PVA, and PVB with a high saponification degree. When the resin composition as a whole is set to 100% by mass, it is preferably 4% by mass or more and 60% by mass or less. From the above viewpoint, it is more preferably 4% by mass or more and 50% by mass or less, and further preferably 5% by mass or more and 50% by mass or less. It should be noted that when using a polyester-polyurethane copolymer, the amount of the polyisocyanate compound added during copolymerization is used as the content of the polyurethane resin.
[0102] In addition, when the resin composition includes an acrylic acid-modified polyester resin and a polyurethane resin, when all the constituent components of the resin composition are set to 100% by mass, the total content of the acrylic acid-modified polyester resin and the polyurethane resin in the resin composition is preferably 30% by mass or more and 90% by mass or less. By making the total content of these resins more than 30% by mass, the adhesion to EVA, PVB, and PVA in a wide range of saponification degrees becomes good, and good adhesion can be maintained even under high temperature and high humidity environments. By making the total content of these components less than 90% by mass, the resin composition can include more than 10% by mass of the following compounds, melamine compounds, and / or compounds with carbodiimide groups, etc., and by including these components, the adhesion to EVA, PVB, and PVA, the flexibility of the resin layer, and toughness are improved, so it is preferred.
[0103] In the case where the acrylic modified polyester resin is not included but the acrylic resin and the polyester resin are included respectively, when all the constituent components of the resin composition are set to 100 mass %, the total content of these components and the polyurethane resin is preferably 30 mass % or more and 90 mass % or less. It should be noted that in this case, by making the resin composition include 10 mass % or more of the compounds described later, melamine compounds and / or compounds having carbodiimide groups, etc., by including these components, the adhesion to EVA, PVB, PVA, the flexibility of the resin layer, and the toughness are improved.
[0104] In addition, when the resin composition includes an acrylic modified polyester resin, the mass ratio of the acrylic modified polyester resin to the polyurethane resin in the resin composition (the content of the acrylic modified polyester resin [parts by mass] / the content of the polyurethane resin [parts by mass]) is preferably 50 / 50 to 90 / 10. As a result, it is easy to adjust the glass transition temperature of the resin layer to a suitable range, and the change in the elastic modulus (ΔP) of the resin layer at 25°C and -20°C can be reduced, so that the change in adhesion to the functional material caused by temperature can be reduced. It should be noted that, when the resin composition does not include an acrylic modified polyester resin but includes an acrylic resin and a polyester resin respectively, it is preferred that the mass ratio of the total of these components to the polyurethane resin is within the above range. In addition, when a polyester-polyurethane copolymer is used, the amount of the polyisocyanate compound added during copolymerization is regarded as the content of the polyurethane resin, and the amount of the polyester polyol compound added during copolymerization is regarded as the content of the polyester resin.
[0105] The inventors' in-depth research results show that the laminated film of the present invention can suppress the separation of the resin layer in the depth direction and easily form a uniform resin layer by making the resin layer contain acrylic resin, polyester resin and polyurethane resin (which can be acrylic modified polyester resin and polyurethane resin, or all of acrylic skeleton, polyester skeleton and polyurethane skeleton), and contain "compounds and chemical structures with both hydrophobic and hydrophilic properties".
[0106] As "compounds and chemical structures having both hydrophobic and hydrophilic properties", oxazoline compounds and chemical structures derived from oxazoline compounds can be cited. That is, the resin layer in the laminated film of the present invention preferably includes a chemical structure derived from an oxazoline compound, or includes an oxazoline compound. By making the resin layer include an oxazoline compound and a chemical structure derived from an oxazoline compound, it is easy to set it to 0.5≤Xs / Xc≤2.0, 0.5≤Xb / Xc≤2.0. Here, the chemical structure derived from the oxazoline compound refers to a chemical structure (compound) in which a cross-linked structure is formed by the oxazoline compound contained in the resin layer, for example, in the case of forming a cross-linked structure with a carboxyl group, it refers to a chemical structure (compound) in which an amide ester bond is formed.
[0107] The oxazoline compound that can be used in the present invention is not particularly limited as long as there is an oxazoline group as a compound of a functional group, preferably containing a copolymer containing an oxazoline group, the copolymer containing an oxazoline group includes at least one structural unit derived from a monomer containing an oxazoline group. As the example of a monomer containing an oxazoline group, 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline etc. can be listed, and they can be used alone or as a mixture of more than two kinds. Wherein, 2-isopropenyl-2-oxazoline is also easily obtained industrially, and is preferred. In addition, the chemical structure derived from the oxazoline compound included in the resin layer of the laminated film of the present invention is preferably derived from the above-mentioned oxazoline compound.
[0108] In oxazoline compound, as other monomers used for addition polymerization oxazoline, namely be used to obtain the monomer outside the monomer containing oxazoline group of the multipolymer containing oxazoline group, as long as can just not have particular restrictions with the monomer copolymerization that contains oxazoline group, be preferably the monomer with hydrophobicity backbone.By making the monomer outside the monomer containing oxazoline group have the hydrophobicity backbone, make the hydrophilic oxazoline group polymerization, can make the oxazoline compound with hydrophobicity and hydrophilicity these two kinds of properties.
[0109] Examples of the monomer having a hydrophobic skeleton include acrylic acid esters or methacrylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, and 2-ethylhexyl methacrylate; unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, and maleic acid; unsaturated nitriles such as acrylonitrile and methacrylonitrile; unsaturated amides such as acrylamide, methacrylamide, N-methylol acrylamide, and N-methylol methacrylamide; vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; olefins such as ethylene and propylene; halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, and vinyl fluoride; and α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene. These monomers may be used alone or as a mixture of two or more thereof.
[0110] In addition, by making resin layer comprise oxazoline compound or be derived from the chemical structure of oxazoline compound, also easily make Δ P be more than 0.2GPa and below 2.0GPa, make elastic modulus ratio P ' be more than 0.1 and below 2.3.Oxazoline compound can form the cross-linked structure for making resin layer firm while keeping flexibility with each component in polyurethane resin, polyester resin, acrylic resin, acrylic acid modified polyester resin, polyester-polyurethane copolymer.Therefore, Δ P, elastic modulus ratio P ' can be made in suitable range.In addition, due to the part in the oxazoline compound contained in resin layer not forming cross-linked structure and remaining in resin layer, therefore, can react with acetyl group, the hydroxyl group of functional material, contribute to improving adhesion.
[0111] The resin layer of the present invention preferably satisfies XO / Xs≥1.0 when the normalized intensities of positive secondary ions of the oxazoline compound of the surface layer and the position of 20% thickness of the resin layer by GCIB-TOF-SIMS are set to XO and XOs, respectively. Satisfying XO / Xs≥1.0 means that the oxazoline compound and the chemical structure derived from the oxazoline compound remain on the surface side of the resin layer, thereby making the water droplet contact angle within a suitable range, resulting in a higher affinity for functional materials and improved adhesion. From the above viewpoints, XO / Xs is more preferably greater than 1.1 and less than 3.0, and further preferably greater than 1.2 and less than 2.5. When XO / Xs satisfies the above preferred range, not only can it be expected that the adhesion to the functional material is improved, but also that the adhesion when the film is rolled up can be reduced.
[0112] Oxazoline compound, from being easily adjusted to preferred range viewpoint by ΔP, elastic modulus ratio P ', being adjusted to preferred range viewpoint by water drop contact angle and being easily satisfied XO / Xs≥1.0 viewpoint, as resin composition when forming resin layer, when the total of acrylic resin, polyester resin, polyurethane resin, acrylic modified polyester resin, polyester-polyurethane copolymer is set to 100 mass parts, more preferably including more than 30 mass parts and less than 90 mass parts, further preferably more than 30 mass parts and less than 70 mass parts, particularly preferably more than 35 mass parts and less than 60 mass parts.In addition, if the content of oxazoline compound is above-mentioned scope, then can expect to reduce the adhesion when film is rolled up in roll shape.It should be noted that, when resin layer comprises these three kinds of skeletons of acrylic skeleton, polyester skeleton and polyurethane skeleton (when meeting feature C), based on the same reason, preferably make the mass ratio of the part comprising these skeletons and the part comprising the chemical structure derived from oxazoline compound in the above-mentioned range.
[0113] In addition, the resin layer may also contain various additives such as melamine compounds and / or compounds with carbodiimide groups, lubricants, inorganic particles, organic particles, surfactants, and surface treatment agents described later as needed. For example, as a resin composition when forming a resin layer, when the total of acrylic resin, polyester resin, and polyurethane resin (or acrylic modified polyester resin and polyurethane resin) is set to 100 parts by mass, the content of the melamine compound is preferably less than 40 parts by mass, and more preferably less than 20 parts by mass. By making the content of the melamine compound and / or the compound with carbodiimide groups less than 40 parts by mass, the properties such as the bendability and toughness of the resin layer can be improved while maintaining the adhesion of the resin layer and the hydrophilic material. Furthermore, in the case of a melamine compound, the adhesion when the film is rolled up in a roll can be reduced, so it is preferred. It should be noted that the melamine compound, in addition to the substance existing as a monomer in the resin layer, also has a substance existing as a part of a cross-linked structure. This is also the same for the compound with carbodiimide groups described later.
[0114] The melamine compound that can be used in the resin layer of the laminated film of the present invention is not particularly limited as long as it has a melamine skeleton. From the viewpoint of solubility as a coating liquid and the planarity of the resin layer, specifically, it is preferred to use a compound obtained by etherifying a hydroxymethylmelamine derivative obtained by condensing melamine with formaldehyde with methanol, ethanol, isopropanol, etc. as a lower alcohol through a dehydration condensation reaction.
[0115] Examples of the methylolated melamine derivatives include monomethylolmelamine, dimethylolmelamine, trimethylolmelamine, tetramethylolmelamine, pentamethylolmelamine, and hexamethylolmelamine.
[0116] As a compound having a carbodiimide group, there is no particular limitation as long as it is a compound having at least one carbodiimide structure represented by the following formula (6) per molecule. From the viewpoint of heat and moisture resistance, etc., a polycarbodiimide compound having two or more carbodiimide groups per molecule is more preferred. In particular, when a polymer isocyanate compound having a plurality of carbodiimide groups at the end or side chain of a polymer such as a polyester resin or an acrylic resin is used, when the resin layer used in the present invention is provided on a film to form a laminated film, not only the hardness of the resin layer is improved, the inhibition of oligomer precipitation is improved, but also the adhesion to various inks, hard coating agents, etc., heat and moisture resistance, flexibility, and toughness are improved.
[0117] Formula (6) -N=C=N-.
[0118] The manufacture of the compound with carbodiimide group can be applicable to known technology, usually by making diisocyanate compound polycondense in the presence of catalyst and obtain.Diisocyanate compound as the starting material of polycarbodiimide compound, aromatic, aliphatic, alicyclic diisocyanate etc. can be used, specifically, toluene diisocyanate, xylene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexyl diisocyanate etc. can be used.And, in the scope that the effect of the present invention is not made to disappear, in order to improve the water solubility and water dispersibility of polycarbodiimide compound, surfactant or hydrophilic monomers such as quaternary ammonium salt, hydroxy alkyl sulfonate of polyalkylene oxide, dialkyl amino alcohol can be added to use.
[0119] In addition, other compounds, for example, well-known cross-linking agents such as epoxy compounds and isocyanate compounds, etc. may be used arbitrarily.
[0120] The laminated film of the present invention preferably has a laminated structure portion that includes at least a layer (A layer) with a polyester resin (resin A) as the main component, and a layer (B layer) with a thermoplastic resin (resin B) different from the above-mentioned resin A as the main component, and laminated with 51 or more layers. The so-called laminated structure portion here refers to a portion where the A layer and the B layer are alternately laminated in a regular arrangement in the thickness direction, for example, a portion laminated in a regular arrangement like A(BA)n (n is a natural number representing the number of repeating units). In addition, the laminated structure portion sometimes also includes a layer (C layer) composed of a third thermoplastic resin, and its arrangement is not particularly limited. For example, a structure in which each layer is laminated in sequence with a certain regularity, such as C(BA)nC, C(ABC)n, C(ACBC)n, etc. (n is a natural number representing the number of repeating units) can be cited. In addition, the so-called 51 or more layers refer to the layers repeated in the laminated structure portion, for example, the total number of A layer and B layer, or A layer and B layer, C layer is 51 or more.
[0121] In order to obtain a laminated film having such a laminated structure, it is preferred to use the film having the above-mentioned laminated structure as a substrate film. Hereinafter, for the purpose of simplifying the description, part of the description will be given by taking a laminated film having a structure formed by alternately laminating layers A and B as one of the preferred embodiments of the present invention as an example, but the same understanding should be made when using three or more thermoplastic resins. It should be noted that, hereinafter, a substrate film having such a laminated structure is sometimes referred to as a multilayer film.
[0122] For example, by using such a multilayer film in a film for a substrate, it is easy to show the function of selectively reflecting light of a specific wavelength band by interference reflection, the function of reflecting light of a specific polarized light, etc., according to the relationship between the difference in the refractive index of each layer and the layer thickness. As a result, by applying a laminated film with such a multilayer film as a substrate to a solar cell back sheet (a sheet for protecting the back of a solar cell), it is possible to impart functions such as heat insulation based on reflection of infrared rays and anti-deterioration function based on reflection of ultraviolet rays to the solar cell. In particular, by improving the heat insulation of the laminated film, the temperature rise of the solar cell caused by direct sunlight and reflected light from the ground surface can be reduced, thereby suppressing the degradation of the solar cell caused by heat, which helps to improve and maintain the power generation efficiency.
[0123] As other uses for laminated films using such multilayer films as substrates, the following examples can be cited. By sandwiching a laminated film having functions such as heat insulation by reflecting infrared rays and deterioration prevention by reflecting ultraviolet rays between two sheets of glass, laminated glass capable of maintaining high heat insulation performance for a long time can be produced. Furthermore, by sandwiching a laminated film having a function of reflecting specific polarized light between two sheets of glass, a member suitable for a display device that displays images with specific polarized light can be produced.
[0124] Here, the so-called resin A is different from resin B, which means that resin A and resin B have different melting points or crystallization temperatures. Different melting points or crystallization temperatures refer to a difference of 3°C or more between the melting point and the crystallization temperature obtained by the measurement method described later. It should be noted that the case where one resin has a melting point and the other resin does not have a melting point, and the case where one resin has a crystallization temperature and the other resin does not have a crystallization temperature are also regarded as having different melting points or crystallization temperatures. For the combination of resin A and resin B, a combination with different melting points and different crystallization temperatures is more preferred.
[0125] In the multilayer film used in the laminated film of the present invention, the difference in the in-plane average refractive index between layer A and layer B is preferably 0.03 or more. More preferably 0.05 or more, and further preferably 0.10 or more. When the difference in the in-plane average refractive index between layer A and layer B is greater than 0.03, sufficient reflectivity can be obtained, so for example, the heat ray cutoff performance is improved. As a method for making the difference in the in-plane average refractive index between layer A and layer B within the above range, a scheme in which one of resins A and B is set to be crystalline and the other to be amorphous can be cited. The crystallinity mentioned here refers to a melting enthalpy of 10 J / g or more in differential scanning calorimetry (DSC). On the other hand, amorphous also refers to a melting enthalpy of less than 10 J / g. In the case of such a resin combination, the refractive index difference can be easily set in the stretching and heat treatment steps in the manufacture of the film.
[0126] The combination of resin A and resin B constituting the multilayer film used in the laminated film of the present invention is preferably a combination having the same basic skeleton. The basic skeleton referred to herein refers to the structure containing the most repeating units constituting the resin. For example, when polyethylene terephthalate is used as a thermoplastic resin, the basic skeleton of another thermoplastic resin is also preferably a polyethylene terephthalate unit from the viewpoint of easily achieving a high-precision laminated structure. If resins A and B are resins containing the same basic skeleton, the lamination accuracy becomes high and interlayer peeling is not easily generated at the lamination interface.
[0127] In addition, as a preferred combination of resin A and resin B of the multilayer film used in the laminated film of the present invention, a combination with a glass transition temperature difference of 20°C or less can be cited. When the difference in glass transition temperature between the two is greater than 20°C, the thickness during the manufacture of the multilayer film sometimes becomes more uneven, resulting in a poor appearance of the final laminated film. In addition, problems such as overstretching sometimes occur when molding the multilayer film. In addition, among resins A and B, it is also preferred that the glass transition temperature of the crystalline resin is lower than the glass transition temperature of the amorphous resin. In this case, when the crystalline resin is stretched at an appropriate stretching temperature in order to orient and crystallize the crystalline resin in the multilayer film, the orientation of the amorphous resin can be suppressed compared to the crystalline resin, and the difference in the average refractive index in the plane can be easily set.
[0128] In the multilayer film used in the laminated film of the present invention, the dicarboxylic acid unit of the polyester resin used as the resin A, the resin B, and the resin C as the main component of the C layer which may be provided as required may include structural units such as terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid (1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid), 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexane dicarboxylic acid, and ester-forming derivatives thereof. These acid components may be used alone or in combination of two or more, and may be partially copolymerized with an oxygen-containing acid such as hydroxybenzoic acid.
[0129] In addition, examples of diol units that can be used for these resins include structural units such as ethylene glycol, 1,2-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 1,5-pentanediol, diethylene glycol, polyalkylene glycol, 2,2-bis(4'-β-hydroxyethoxyphenyl)propane, isosorbide, 1,4-cyclohexanedimethanol, spiro glycol, neopentyl glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, triethylene glycol, tetraethylene glycol, polytetramethylene ether glycol, and ester-forming derivatives thereof.
[0130] As dicarboxylic acid units constituting these resins, preferably, there can be mentioned structural units such as terephthalic acid, 2,6-naphthalene dicarboxylic acid, and isophthalic acid, and as diol units, preferably, there can be mentioned structural units such as ethylene glycol, 1,4-cyclohexanedimethanol, polyalkylene glycol, polyethylene glycol, tetraethylene glycol, and polytetramethylene ether glycol. These diol components may be used alone or in combination of two or more.
[0131] As an example of a preferred combination of resins A and B that satisfies the above-mentioned glass transition temperature condition, there can be cited an example in which one of the resins A and B is polyethylene terephthalate or polyethylene naphthalate, and the other is a polyester formed by a polyester derived from spirodiol. The polyester derived from spirodiol is a polyester using spirodiol as a diol component, and refers to a copolymer with other ester structural units, a polyester using spirodiol as a single diol component, or a polyester blended with other polyester resins and preferably having spirodiol residues accounting for more than half of all diol residues in the polyester resin. The polyester derived from spirodiol has a small difference in glass transition temperature from polyethylene terephthalate and polyethylene naphthalate, so it is not easy to over-stretch during molding, and it is also not easy to cause interlayer delamination, so it is preferred.
[0132] From the above viewpoints, it is preferred that one of the resins A and B is polyethylene terephthalate or polyethylene naphthalate, and the other is a polyester using spiroglycol and cyclohexanedicarboxylic acid. When the polyester obtained using spiroglycol and cyclohexanedicarboxylic acid is used in one layer, the difference in in-plane refractive index with polyethylene terephthalate and polyethylene naphthalate becomes large, so it is easy to obtain a high reflectivity. In addition, the difference in glass transition temperature with polyethylene terephthalate and polyethylene naphthalate is small, and the adhesion is also excellent, so it is not easy to over-stretch during molding, and it is not easy to peel between layers.
[0133] In addition, in the multilayer film used in the laminated film of the present invention, it is also preferred that one of the resins A and B is polyethylene terephthalate or polyethylene naphthalate, and the other is a polyester derived from cyclohexanedimethanol. The polyester derived from cyclohexanedimethanol refers to a polyester using cyclohexanedimethanol as a diol component, a copolymer with other ester structural units, a polyester using cyclohexanedimethanol as a single diol component, or a polyester blended with other polyesters, and a polyester in which cyclohexanedimethanol residues account for more than half of all diol residues. The polyester derived from cyclohexanedimethanol has a small difference in glass transition temperature from polyethylene terephthalate and polyethylene naphthalate, so it is not easy to over-stretch during molding, and it is not easy to cause interlayer delamination, so it can be preferably used. It is more preferred that at least one thermoplastic resin is a polycondensate of polyethylene terephthalate in which the copolymerization amount of cyclohexanedimethanol is 15 mol% or more and 60 mol% or less.
[0134] By setting such a scheme, while having high reflectivity, the change of optical properties caused by heating and time will be reduced, and interlayer peeling is not easy to occur. Furthermore, the ethylene terephthalate condensation product with a copolymerization amount of cyclohexanedimethanol of more than 15 mol% and less than 60 mol% can be very strongly bonded to polyethylene terephthalate. In addition, for the cyclohexanedimethanol group, there are cis-isomers or trans-isomers as geometric isomers, and there are chair-type and boat-type conformational isomers. Therefore, even if it is co-stretched with polyethylene terephthalate, it is not easy to be oriented and crystallized. Therefore, the obtained film has a high reflectivity, and the change of optical properties caused by the thermal history is less, and it is not easy to break during film making.
[0135] Resins with different melting points and crystallization temperatures usually have different optical properties. Therefore, by alternately laminating such resins, according to the relationship between the difference in the refractive index of each layer and the layer thickness, it is easy to make the light reflection of a specific wavelength region. In addition, the more the number of layers of the laminate, the more high reflectivity can be obtained in a wide band. From this viewpoint, the number of layers of the laminated structure part is preferably 51 layers, more preferably more than 201 layers, and more preferably more than 401 layers. In such reflection (interference reflection), as the total number of layers of the A layer and the B layer increases, the wavelength region widens, and the reflectivity becomes higher, so a laminated structure part with high light cut-off performance can be obtained. Therefore, although there is no upper limit to the number of layers of the laminated structure part, as the number of layers of the laminated structure part increases, the increase in manufacturing cost and the deterioration of operability caused by the thickening of the film thickness caused by the large-scale manufacturing device are generated, so in fact, within a total of 1001 layers is a practical range.
[0136] The laminated film of the present invention preferably has a wavelength with a reflectivity of 30% or more, more preferably a wavelength with a reflectivity of 50% or more, and further preferably a wavelength with a reflectivity of 80% or more, when light with a wavelength of 300nm to 2500nm is incident at an incident angle of 10°C on at least one surface from the viewpoint of improving reflective properties such as heat insulation. Furthermore, from the same viewpoint, when light with a wavelength of 300nm to 2500nm is incident at an incident angle of 10°C on at least one surface, it preferably has at least one reflection band with a reflectivity of 30% or more continuously over a wavelength width of 20nm or more, more preferably a wavelength width of 100nm or more, and further preferably a wavelength width of 300nm or more.
[0137] The reflectivity at each wavelength can be measured as a relative reflectivity based on an alumina white plate, and the details are described later. In addition, the angle of incidence refers to the angle formed with the normal line of the film surface. "On at least one surface" means that the conditions are satisfied when the reflectivity is measured by irradiating light to at least one surface, and preferably the conditions are satisfied when the reflectivity is measured by irradiating light to the surface on one side of the resin layer. Below, the same explanation is given for "on at least one surface" in the measurement of optical properties.
[0138] Such characteristics can be achieved by using a multilayer film as a substrate film and increasing the difference in the average in-plane refractive index between layer A and layer B. Therefore, when the multilayer film is made into a biaxially stretched film, it is preferably made into a multilayer polyester film in which a layer mainly composed of a crystalline polyester resin and a layer mainly composed of a low refractive index copolyester which remains amorphous during stretching or melts in a heat treatment step are alternately laminated.
[0139] The laminated film of the present invention preferably has an average reflectivity of 15% or less in the wavelength band of 400nm to 700nm and an average reflectivity of 70% or more in the wavelength band of 850nm to 1200nm when light is incident at an incident angle of 10° on at least one side. By setting it as such, it is possible to suppress reflection in the visible region, reduce coloration or glare, and reflect infrared rays. Therefore, such a laminated film has excellent heat insulation properties. For example, by sandwiching such a laminated film between two sheets of glass, a laminated glass that can maintain high heat insulation performance for a long time can be obtained.
[0140] A laminated film having an average reflectivity of 70% or more in the wavelength band of 850 to 1200 nm can be obtained, for example, by using a multilayer film as a substrate film for the laminated film, increasing the total number of layers of layer A and layer B, and / or increasing the average in-plane refractive index difference between layer A and layer B. The total number of layers also depends on the average in-plane refractive index difference between layer A and layer B (or the resins A and B as the main components of these layers), and the total number of layers A and layer B is preferably 201 or more. By making the total number of layers A and B 201 or more, it is easy to make the average reflectivity of the wavelength band of 850 to 1200 nm 70% or more. In addition, when the average reflectivity of the wavelength band of 850 to 1200 nm is set to 80% or more, it is preferred to set the total number of layers A and layer B to 401 or more.
[0141] In order to obtain such a laminated film, for more than half of the layers constituting the multilayer film (laminated structure portion) used as the substrate of the laminated film, the sum of the optical thickness of the adjacent layers is preferably 400 to 700 nm. The optical thickness mentioned here refers to the product of the layer thickness of each layer and the refractive index of the resin constituting the layer, and the sum of the optical thickness of the adjacent layers becomes a factor that determines the wavelength of interference reflection in the laminated film. Interference reflection caused by a laminated structure portion such as a laminated structure portion in which the sum of the optical thickness of adjacent layers is 400 to 700 nm usually occurs in a wavelength range of about 800 to 1400 nm, so it is easy to make the average reflectivity of the wavelength band of 850 to 1200 nm to be 70% or more. In addition, the greater the number of layers and the difference in the average refractive index of the adjacent layers, the greater the reflectivity. For more than half of the layers, in a multilayer film having a laminated structure portion in which the sum of the optical thickness of the adjacent layers is 400 to 700 nm, it is easy to effectively improve the average reflectivity of the wavelength band of 850 to 1200 nm.
[0142] For example, when polyethylene terephthalate having a refractive index of 1.66 and polyethylene terephthalate obtained by copolymerizing spiroglycol and cyclohexanedicarboxylic acid having a refractive index of 1.55 are used as resins A and B, in order to make the average reflectivity in the wavelength range of 850 to 1200 nm 70% or more, the number of layers required for the sum of the optical thicknesses of adjacent layers to be 400 to 700 nm is about 201 or more. As the difference in the in-plane average refractive index between resins A and B increases, the number of layers required to make the maximum value of the reflectivity in the wavelength range of 850 to 1200 nm 70% or more decreases. If the in-plane average refractive index difference is 0.3 or more, sufficient reflectivity can be given even if the number of layers is about 51. When polyethylene terephthalate having a refractive index of 1.66 and polyethylene terephthalate obtained by copolymerizing spiroglycol and cyclohexanedicarboxylic acid having a refractive index of 1.55 are used as thermoplastic resins, the layer thickness required to make the sum of the optical thicknesses of adjacent layers 400 to 700 nm is in the range of about 120 to 220 nm.
[0143] As another example of forming a laminate film having an average reflectance of 70% or more in the wavelength range of 850 to 1200 nm, the optical thicknesses of the adjacent A layer and B layer may satisfy the following formula (7) and formula (8) at the same time.
[0144] λ=2(n α d α +n β d β ) (7)
[0145] n α d α =n β d β (8)
[0146] Here, λ is the reflection wavelength, n α is the in-plane refractive index of layer A, d α is the thickness of layer A, n β is the in-plane refractive index of layer B, d β is the thickness of layer B. By having a layer thickness distribution that satisfies both formula (7) and formula (8), even-numbered reflections can be eliminated. Therefore, the average reflectivity in the range of wavelengths of 850nm to 1200nm can be increased while the average reflectivity in the range of wavelengths of 400 to 700nm as the visible light region can be reduced, so that a transparent film with high heat ray blocking performance can be obtained. Usually, the refractive index of the film after molding and stretching the thermoplastic resin is about 1.4 to 1.9. Therefore, by making the ratio of the thickness of the adjacent A layer to the B layer (the thickness of the A layer / the thickness of the B layer) be greater than 0.7 and less than 1.4, a film that suppresses even-numbered reflections can be obtained. Therefore, it is preferred that the ratio of the thickness of the adjacent A layer to the B layer (the thickness of the A layer / the thickness of the B layer) be set to greater than 0.7 and less than 1.4. More preferably, it is greater than 0.8 and less than 1.2.
[0147] As one embodiment of the multilayer film used in the laminated film of the present invention, there can be cited an embodiment in which the refractive index of at least one surface of the laminated polyester film is 1.68 or more and 1.80 or less. When the refractive index is lower than 1.68, it is sometimes difficult to have a reflection band with a reflectivity of 30% or more over 20 nm in the wavelength range of 300 nm to 2500 nm. When the refractive index is higher than 1.80, the difference in chemical structure becomes larger, thereby deteriorating the lamination property of resin A and resin B, and sometimes the turbidity of the multilayer film and the peeling at the interface between layer A and layer B become significant.
[0148] As an example of a method for making the refractive index of at least one surface of the multilayer film be 1.68 or more and 1.80 or less, there can be mentioned a method in which the main dicarboxylic acid unit of the resin A is a naphthalene dicarboxylic acid unit. By setting such a scheme, the refractive index difference between the A layer and the B layer can be set, and a laminated polyester film with more excellent reflective performance can be easily obtained. In addition, in order to increase the refractive index difference between the A layer and the B layer, the resin B is also preferably an amorphous resin. In order to make the resin A of the laminated polyester film of the present invention contain naphthalene dicarboxylic acid in the dicarboxylic acid constituent component, a method in which naphthalene dicarboxylic acid is included in the dicarboxylic acid constituent component of the raw material polyester resin constituting the resin A can be adopted.
[0149] The laminated film of the present invention preferably has an average transmittance of vertically incident visible light of 50% or more and 100% or less on at least one surface, and when the average reflectivity (%) of P-wave light with a wavelength of 400nm to 700nm is set to R20, R40, and R70 relative to the normal to the film surface at angles of 20°, 40°, and 70°, the relationship of R20≤R40<R70 is satisfied.
[0150] Here, perpendicular refers to an angle of 0° with respect to the film surface itself or a cut surface of the film surface. By making the average transmittance of vertically incident visible light with a wavelength of 400 to 700 nm 50% or more and 100% or less, the laminate film has the same transparency as transparent glass and transparent resin film. Therefore, when such a laminate film is sandwiched between two sheets of glass to form a laminated glass, good visibility of the background can be obtained when the background is observed from a direction perpendicular to the laminated glass.
[0151] From the above viewpoints, the transmittance is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. If the transmittance is 90% or more, when the background is observed from a direction perpendicular to the laminated glass, the background can be visually recognized without feeling the presence of the laminated glass. It should be noted that from the viewpoint of feasibility, the upper limit of the transmittance is preferably 99%.
[0152] The transmittance of light perpendicularly incident on the laminate film can be determined by measuring the transmittance of light with a wavelength of 400 to 700 nm at an incident angle θ = 0° in units of 1 nm using a spectrophotometer and calculating the average value, for which detailed measurement conditions are described in the examples below.
[0153] In addition, when the average reflectivity (%) of the P wave with a wavelength of 400nm to 700nm is set to R20, R40, and R70 when the P wave light is incident at an angle of 20°, 40°, and 70° relative to the normal line of the film surface, the solution that satisfies the relationship of R20≤R40<R70 is a solution in which the laminated film does not have an angle equivalent to the Brewster angle. In the case of a common transparent substrate such as transparent glass and a transparent resin film, as the incident angle with respect to the normal line of one surface of the transparent substrate gradually increases from 20°, the reflectivity of the P wave, which is one of the polarized lights, decreases, and at an angle called the Brewster angle, the reflectivity is 0%. Therefore, for a common transparent substrate, it is difficult to transmit the P wave in the front direction and reflect it in the oblique direction.
[0154] When the reflectance of each P wave is set to R20, R40, and R70 when incident at an angle of 20°, 40°, and 70° relative to the normal line of the film surface on at least one surface of the laminated film, and the relationship of R20≤R40<R70 is satisfied, the laminated film is suitable for a display device that displays images using light from the P wave in an oblique direction. From the perspective of making the image display property good, R70 is preferably 30% or more, and more preferably 50% or more. As R70 increases, the display property of the projected image increases when the image of the P wave is projected onto the surface of the projected image display component. It should be noted that the upper limit of R70 is not particularly limited, and is 99% from the perspective of feasibility.
[0155] It should be noted that regarding the average reflectivity (%) of the P wave, the detailed measurement conditions are described in the following examples. It can be determined by using a spectrophotometer to measure the reflectivity of the P wave in the wavelength range of 400 to 700 nm when the incident angles θ = 20°, 40°, and 70° in units of 1 nm, and calculating the average value.
[0156] For a laminated polyester film, the transmittance of visible light perpendicularly incident on the film surface is set to be greater than 50% and less than 100%, and the reflectivity (%) of each P wave when incident at angles of 20°, 40°, and 70° relative to the normal to the film surface is set to R20, R40, and R70 so as to satisfy the relationship of R20≤R40<R70, and R70 is set to be greater than 10%. The details are described below as an example of a method.
[0157] The average transmittance of visible light perpendicularly incident on the laminated polyester film can be reduced by reducing the refractive index difference between the two thermoplastic resin layers in the direction parallel to the film surface (in-plane direction). For example, if the number of layers of the laminated polyester film is within the above range, if the refractive index difference in the direction parallel to the film surface is 0.06 or less, it is easy to make the transmittance 50% or more, if it is 0.04 or less, it is easy to make the transmittance 70% or more, and if the refractive index difference is 0.02 or less, it is easy to make the transmittance 80% or more. It should be noted that the "refractive index difference in the direction parallel to the film surface" refers to the absolute value of the difference in the in-plane refractive index between adjacent thermoplastic resin layers.
[0158] In order to obtain a laminated polyester film satisfying the relationship of R20≤R40<R70, a method of adjusting the refractive index difference between two thermoplastic resin layers in the direction perpendicular to the film surface and the number of layers can be adopted. In this case, the greater the refractive index difference in the direction perpendicular to the film surface and the greater the number of layers, the greater R70 can be. For example, when the number of layers reaches 801, if the refractive index difference in the direction perpendicular to the film surface is 0.08 or more, it is easy to make the reflectivity 30% or more, and if the refractive index difference is 0.12 or more, it is easy to make the reflectivity 50% or more. As a result, when the reflectivity (%) of each P wave is set to R20, R40, and R70 when incident at an angle of 20°, 40°, and 70° relative to the normal line of the laminated polyester film, the relationship of R20≤R40<R70 can be satisfied. In addition, even if the refractive index difference does not reach the above level, the reflectivity can be increased by further increasing the number of layers to reach the above level. In addition, the refractive index in the direction perpendicular to the film surface may be referred to as the surface perpendicular refractive index below.
[0159] The method of adjusting the reflection wavelength of the laminated film to a wavelength range of 400 to 700 nm can include adjusting the perpendicular refractive index difference between the two thermoplastic resin layers, the number of layers, the layer thickness distribution, the film forming conditions (such as stretching ratio, stretching speed, stretching temperature, heat treatment temperature, heat treatment time), etc. For the layer thickness distribution, it is preferred that the optical thickness of the adjacent A layer and B layer satisfy the formula (7). It should be noted that the crystalline thermoplastic resin in the A layer and the amorphous thermoplastic resin in the B layer are preferably polyesters.
[0160] λ=2(n α d α +n β d β ) (7)
[0161] The layer thickness distribution of the multilayer film used in the laminated film of the present invention is preferably set to a constant layer thickness distribution from one side of the laminated polyester film surface to the opposite side, a layer thickness distribution set to increase or decrease from one side of the laminated polyester film surface to the opposite side, a layer thickness distribution set to increase first and then decrease from one side of the laminated polyester film surface toward the center of the film, a layer thickness distribution set to decrease first and then increase from one side of the laminated polyester film surface toward the center of the film, or a distribution combining these distributions. As a method of changing the layer thickness distribution, a continuous change method such as a linear, geometric, or step difference series, and a method in which 10 to 50 layers have approximately the same layer thickness and the layer thickness changes in a step-like manner are preferred.
[0162] On the two surface layers of the multilayer film used in the laminated film of the present invention, a layer with a thickness of more than 1% of the thickness of the multilayer film itself can be preferably provided as a protective layer, and the thickness of each protective layer is preferably more than 4% relative to the total thickness of the multilayer film. By thickening the thickness of the protective layer, it is related to the suppression of flow marks during film making, the improvement of the accuracy of the actual layer thickness of each layer relative to the design, the lamination process with other films and molded bodies and the suppression of deformation of the thin film layer in the multilayer film after the lamination process, and the pressure resistance. It should be noted that from the perspective of suppressing the increase in the thickness of the multilayer film and ensuring the laminated structure portion required for the presentation of interference reflection, the upper limit of the thickness of the protective layer is 20%. The thickness of the multilayer film is not particularly limited, for example, it is preferably 20. μ m~300 μ m. If it is 20 μ m or more, the rigidity of the multilayer film becomes strong and the operability can be ensured. μ When m is less than or equal to, the rigidity of the multilayer film does not become too high, and the moldability is improved.
[0163] As an example of a laminated polyester film preferably used in the present invention, when the direction parallel to the film surface and the direction in which the average rate of change of the heat shrinkage measured by thermomechanical analysis in the range of 100°C to 150°C is the largest is set as the X direction, the average rate of change of the heat shrinkage in the X direction is preferably 0.01% / °C or more and 0.1% / °C or less. The thermomechanical analysis mentioned here refers to a method of measuring the deformation of a substance as a function of temperature while applying a non-vibrating load while changing the temperature of the substance according to an adjusted program, and is measured using a commercially available thermomechanical analysis device. In addition, the heat shrinkage is defined by formula (9).
[0164] In addition, the average rate of change of heat shrinkage mentioned here refers to the value obtained by dividing the difference between the heat shrinkage at 100°C and 150°C by the temperature difference. By making the laminated polyester film such a scheme, when the laminated polyester film is sandwiched between two intermediate layers and two glasses to form a laminated glass, wrinkles and peeling can be suppressed, and a laminated glass with good appearance can be obtained. More preferably, the average rate of change of heat shrinkage is 0.01% or more and less than 0.05%. In addition, it is also preferred to set the direction orthogonal to the X direction as the Y direction, and in any direction of the X direction and the Y direction, the average rate of change of heat shrinkage measured by thermomechanical analysis in the range of 100°C to 150°C is 0.01% / °C or more and 0.1% / °C or less. In this case, since the heat shrinkage changes isotropically, it can more appropriately follow the change of the heat shrinkage of the intermediate layer, and the generation of wrinkles and peeling can also be basically suppressed.
[0165] For a laminated film, when the direction with the largest average rate of change of heat shrinkage measured by thermomechanical analysis in the range of 100°C to 150°C is set as the X direction, in order to make the average rate of change of heat shrinkage in the X direction 0.01% / °C or more and 0.1% / °C or less, in the manufacture of the laminated film, it is preferred to enhance the orientation in the length direction of the film by adjusting the longitudinal stretching ratio and the longitudinal stretching temperature. For example, in the case of using a multilayer film as a substrate film for a laminated film, by making the longitudinal stretching temperature below 90°C or making the longitudinal stretching ratio above 3.5 times, the desired multilayer film is easily obtained. Similarly, it is also preferred to enhance the orientation in the direction orthogonal to the length direction by the transverse stretching temperature and the transverse stretching ratio. For example, in the case of using a multilayer film as a substrate film for a laminated film, by making the transverse stretching temperature below 110°C or making the transverse stretching ratio above 3.8 times, the desired multilayer film is easily obtained. In addition, in order to suppress the difference in heat shrinkage behavior in the length direction of the multilayer film and in the direction orthogonal thereto, it is preferred to adjust the longitudinal stretching conditions and the transverse stretching conditions. Specifically, by setting the difference between the longitudinal stretching ratio and the transverse stretching ratio to 0.3 times or less and the temperature difference between the longitudinal stretching temperature and the transverse stretching temperature to 20° C. or more, it is easy to make the heat shrinkage behavior isotropic. These methods can be used in combination as appropriate, and by using the multilayer film obtained in this way as a substrate film, a laminated film having an average change rate of heat shrinkage in the X direction of 0.01% / ° C. or more and 0.1% / ° C. or less can be obtained.
[0166] In addition, when there is a difference in melting point between resin A and resin B, it is also preferable to set the heat treatment temperature after stretching to a temperature between the melting points of the two. In this case, the resin with a relatively high melting point maintains a high orientation state, while the orientation of the other resin is relaxed, so it is easy to set the refractive index difference between these resins, and it is also possible to impart high thermal shrinkage behavior to the thermoplastic resin that maintains the orientation. In addition, when resin A is a crystalline polyester and resin B is a polyester resin containing amorphous polyester and crystalline polyester, the heat treatment temperature is preferably less than the crystalline polyester contained in resin A and resin B. In this case, in addition to the orientation of resin A, the orientation of the crystalline polyester contained in resin B is also maintained, so a higher thermal shrinkage behavior can be imparted.
[0167] In addition, the relaxation treatment is performed to suppress the heat shrinkage behavior, so it is also preferred not to perform the relaxation treatment. As for the preferred degree of relaxation treatment, the ratio of the relaxation treatment to the film width before the relaxation treatment is 0% or more and 5% or less (the relaxation treatment ratio of 0% means that the relaxation treatment itself is not performed). Although it also depends on the types of the laminated resins A and B, if it is, for example, polyethylene terephthalate and an amorphous polyester that is completely melted in the heat treatment step, a multilayer film with good heat shrinkage behavior can be obtained within the range of about 0% to 1% of the relaxation treatment ratio relative to the film width before the relaxation treatment.
[0168] Here, the length direction refers to the running direction of the sheet or film (the winding direction of the film in the case of a film roll), and the width direction refers to the direction orthogonal to the length direction in the film surface. Generally speaking, the heat shrinkage rate exists as a residual stress relative to the tensile stress, and the heat shrinkage rate becomes larger. Therefore, any direction in the length direction or the width direction is the X direction, and the other direction is the Y direction.
[0169] The laminated film of the present invention preferably has a micro-endothermic peak determined by differential scanning calorimetry at 170°C or more and 210°C or less. The micro-endothermic peak is an endothermic peak corresponding to the thermal history of the heat treatment temperature during transverse stretching described later, and the thermal shrinkage of the laminated film varies according to the temperature of the endothermic peak. By making the micro-endothermic peak above 170°C and below 210°C, the shrinkage of the laminated film is similar to that of EVA, PVB, and PVA, so that wrinkles can be suppressed in thermal processing processes such as laminate vitrification. The micro-endothermic peak is usually observed on the low temperature side lower than the melting point and near the melting point, and is observed in the first run of the differential scanning calorimetry. Since it was not observed in the second round in which the temperature was once raised to above the melting point and the thermal history was eliminated, the position of the micro-endothermic peak can be confirmed by comparing the peaks of the two. It should be noted that the determination method of the micro-endothermic peak is as described below.
[0170] Hereinafter, a preferred method for producing a laminated film will be described by taking a multilayer film using polyethylene terephthalate as the resin A constituting the A layer and a copolymer of polyethylene terephthalate (polyethylene terephthalate copolymerized with 20 to 40 mol% of cyclohexanedimethanol) as the resin B constituting the B layer as an example of a substrate film. Of course, the laminated film of the present invention should not be construed as being limited to the above example. Furthermore, the laminated structure of the multilayer film can be easily realized by the same method as described in paragraphs
[0053] to
[0063] of Japanese Patent Application Laid-Open No. 2007-307893.
[0171] Prepare each resin in the form of particles. For the particles, after drying in hot air or under vacuum as needed, supply them to each extruder. In the extruder, for the resin heated and melted at 280-300°C, a gear pump or the like is used to make the extrusion amount of the resin uniform, and foreign matter, deteriorated resin, etc. are removed by means of a filter or the like. After these resins are formed into a target shape using a die head, they are discharged. Then, the sheet laminated into multiple layers discharged from the die head is extruded onto a cooling body such as a casting drum, and becomes a cast film after cooling and solidifying. At this time, it is preferred to use a linear, strip-shaped, needle-shaped or knife-shaped electrode, and utilize electrostatic force to make it close to a cooling body such as a casting drum and quench and solidify it. In addition, it is also preferred to blow air from a slit-shaped, point-shaped, or planar device to make it close to a cooling body such as a casting drum and quench and solidify it, or to use a clamping roller to make it close to a cooling body and quench and solidify it.
[0172] At this time, resin A and resin B are melt-kneaded with different extruders and fed into a multilayer laminating device from different flow paths. As a multilayer laminating device, a multi-manifold die head, a feed block, a static mixer, etc. can be used. In particular, in order to efficiently obtain the structure of the present invention, a feed block with 51 to 1001 fine slits is preferably used. When using such a feed head, the device will not be extremely large-scale, so there are few foreign bodies caused by thermal degradation. If the number of layers is 51 to 1001 layers, high-precision lamination can be achieved. In addition, compared with the prior art, the lamination accuracy in the width direction is also significantly improved. In addition, in such a feed head, the thickness of each layer can be adjusted by the shape (length, width) of the slit, so it is also easy to achieve any layer thickness. The molten multilayer laminate formed into the desired layer structure is guided to the die head to obtain a cast film as described above.
[0173] The cast film thus obtained is preferably subjected to biaxial stretching. Here, the so-called biaxial stretching refers to stretching in the length direction and the width direction. Stretching can be performed in two directions successively or simultaneously. In addition, re-stretching can also be performed in the length direction and / or the width direction.
[0174] First, the case of successive biaxial stretching is described. In the case of successive biaxial stretching, stretching in the width direction (transverse stretching) is usually performed after stretching in the length direction (longitudinal stretching). Here, stretching in the length direction refers to stretching for imparting molecular orientation in the length direction to the film, which is usually implemented using the difference in the peripheral speed of the roller. The stretching can be performed in one stage, or it can be performed in multiple stages using multiple roller pairs. The stretching ratio varies depending on the type of resin, and is generally preferably 2 to 15 times. When polyethylene terephthalate is used as resin A, 2 to 7 times is particularly preferably used. In addition, the stretching temperature is preferably the glass transition temperature of the resin constituting the film to the glass transition temperature + 100°C.
[0175] The thus obtained uniaxially stretched film is subjected to a surface treatment such as corona treatment, flame treatment, plasma treatment, etc. as necessary, and then subjected to a step of coating a resin composition to form a resin layer. The details of the method for forming the resin layer will be described later.
[0176] Next, the stretching in the width direction refers to the stretching used to give the film an orientation in the width direction. Usually, a tenter is used. For the uniaxially stretched film obtained by longitudinal stretching, the two ends of the film in the width direction are clamped with multiple clamps while being transported, and the interval between the opposing clamps is expanded, thereby stretching in the width direction. As the stretching ratio, it varies according to the type of resin, and is usually preferably 2 to 15 times. When polyethylene terephthalate is used as resin A, it is particularly preferably 2 to 7 times. In particular, for the laminated film of the present invention, the transverse stretching ratio is preferably set to 4 times or more. By increasing the transverse stretching ratio, it is effective to improve the uniformity of the reflection band and the uniformity of the average reflectivity. In addition, as the stretching temperature, it is preferably the maximum glass transition temperature of the resin constituting the film to the maximum glass transition temperature + 120°C.
[0177] For the film that has been biaxially stretched like this, in order to impart planarity and dimensional stability, it is preferably heat-treated in a tenter at a temperature above the stretching temperature and below the melting point of the thermoplastic resin A. By heat-treating, the dimensional stability of the film improves. After the film is heat-treated like this, it is evenly and slowly cooled, cooled to room temperature and wound up. In addition, it is also possible to use relaxation treatment etc. when slowly cooling from the heat treatment as needed.
[0178] Next, the case of simultaneous biaxial stretching is described. In the case of simultaneous biaxial stretching, the obtained cast film is subjected to surface treatment such as corona treatment, flame treatment, plasma treatment, etc. as necessary, and then a resin layer is formed by in-line coating.
[0179] Next, the cast film is guided to a simultaneous biaxial tenter, and the two ends of the film are clamped with a clamp while being transported, and the film is stretched simultaneously and / or in stages in the length direction and the width direction. The tenter that can be used as a simultaneous biaxial stretching machine includes a zooming method, a screw method, a drive motor method, and a linear motor method. Preferably, the drive motor method or the linear motor method that can arbitrarily change the stretching ratio and can perform relaxation treatment at any position is used. As a stretching ratio, it varies according to the type of resin. Usually, as an area ratio, it is preferably 6 to 50 times. When polyethylene terephthalate is used as the thermoplastic resin A, it is particularly preferably 8 to 30 times as an area ratio. In particular, in the case of simultaneous biaxial stretching, in order to suppress the orientation difference in the plane, it is preferred to make the stretching ratio in the length direction and the width direction the same, and to make the stretching speed approximately equal. In addition, as a stretching temperature, it is preferably the maximum glass transition temperature of the resin constituting the film to the maximum glass transition temperature + 120°C.
[0180] In order to impart planarity and dimensional stability to the biaxially stretched film, it is preferred to continue to perform heat treatment above the stretching temperature and below the melting point in the tenter. During this heat treatment, in order to suppress the distribution of the main orientation axis in the width direction, it is preferred to perform relaxation treatment in the length direction immediately before entering the heat treatment zone and / or immediately after entering the heat treatment zone. After the film is heat treated like this, it is cooled evenly and slowly, and then cooled to room temperature and wound up. In addition, it can be relaxed in the length direction and / or in the width direction when slowly cooling from the heat treatment as needed. It is preferred to perform 1 to 5% relaxation treatment in the length direction immediately before entering the heat treatment zone and / or immediately after entering the heat treatment zone.
[0181] As a method for forming a resin layer on the multilayer film thus obtained, a method for forming a resin layer by applying a resin composition on at least one surface of the multilayer film can be used. In this method, the resin composition comprises a polyurethane resin, an acrylic modified polyester resin (or an acrylic resin and a polyester resin). It is further preferred that the resin composition comprises an oxazoline compound. When such a resin composition is applied to a thermoplastic resin film, a solvent may be included in the resin composition. That is, each resin component may be dissolved or dispersed in a solvent to form a coating solution, which is applied to the multilayer film. After coating, the solvent is dried and heated, thereby obtaining a laminated film laminated with a resin layer. In the present invention, as a solvent, an aqueous solvent is preferably used. This is because by using an aqueous solvent, the rapid evaporation of the solvent in the heating process can be suppressed, and not only a uniform resin layer can be formed, but also excellent in terms of environmental load.
[0182] Here, the aqueous solvent refers to water, or a solvent obtained by mixing water with a water-soluble organic solvent such as alcohols such as methanol, ethanol, isopropanol, and butanol, ketones such as acetone and methyl ethyl ketone, and glycols such as ethylene glycol, diethylene glycol, and propylene glycol in any ratio.
[0183] For the coating method of the resin composition on the multilayer film, any one of the online coating method and the offline coating method can be used, preferably the online coating method. The online coating method refers to a method for coating in the manufacturing process of the film. Specifically, it refers to a method for coating at any stage from the time when the thermoplastic resin is melt-extruded to the time when it is rolled up, and is usually coated on a substantially amorphous unstretched (unoriented) polyester film (A film) obtained by quenching after melt extrusion, a uniaxially stretched (uniaxially oriented) polyester film (B film) stretched in the length direction thereafter, or a biaxially stretched (biaxially oriented) polyester film (C film) before the heat treatment further stretched in the width direction.
[0184] In the present invention, the following method is preferably used, that is, a resin composition is applied to any of the A film and the B film as the polyester film before the crystal orientation is completed, the solvent is evaporated, and then the polyester film is stretched in a uniaxial direction or a biaxial direction, and heated to complete the crystal orientation of the polyester film and provide a resin layer. According to this method, the production of the substrate film, the application of the resin composition, the drying of the solvent, and the heating (i.e., the formation of the resin layer) can be carried out at the same time, so there is an advantage in terms of manufacturing cost. In addition, since the stretching is performed after the coating, it is also easy to make the thickness of the resin layer thinner.
[0185] Among them, the method of coating the resin composition on a film (B film) that has been uniaxially stretched in the length direction, drying the solvent, and then stretching in the width direction and heating is excellent. This is because compared with the method of coating on an unstretched film and then biaxially stretching, the stretching process after coating is one less, so it is not easy to produce defects and cracks in the resin layer caused by stretching, and a resin layer with excellent transparency and smoothness can be formed.
[0186] On the other hand, the off-line coating method refers to a method of coating the resin composition on the film after the above-mentioned A film is stretched uniaxially or biaxially and subjected to heat treatment to complete the crystal orientation of the polyester film, or on the A film in a process different from the film manufacturing process. In the present invention, it is preferably set by the online coating method based on the above-mentioned various advantages.
[0187] The most preferred method for forming the resin layer in the present invention is a method in which a resin composition using an aqueous solvent is applied onto a polyester film by an in-line coating method, and the aqueous solvent is heated and dried to form the resin layer.
[0188] When making the resin layer to form the resin combination used, the solvent preferably uses an aqueous solvent. For resin combination, it is possible to mix and stir the acrylic modified polyester resin (acrylic resin and polyester resin) of water dispersion or water dissolution, polyurethane resin, oxazoline compound and / or melamine compound and aqueous solvent in any order and in the desired weight ratio as required. Then, various additives such as lubricant, inorganic particles, organic particles, surfactant, antioxidant, thermal initiator can be mixed and stirred in any order as required so that the characteristic of the resin layer provided by the resin combination does not deteriorate. For the method for mixing and stirring, the container can be shaken by hand, or a magnetic stirrer, stirring blade can be used, or ultrasonic irradiation, vibration dispersion, etc. can be carried out.
[0189] The resin composition can be coated on the laminated film by any known coating method, such as rod coating, reverse coating, gravure coating, die coating, blade coating, etc. From the viewpoint of appropriate coating thickness and viscosity, rod coating and gravure coating are preferred.
[0190] The thickness of the resin layer of the present invention is not particularly limited, but is preferably 20 to 500 nm. By setting the thickness of the resin layer to 20 nm or more, it is easy to provide a uniform resin layer on the substrate film. By setting the thickness of the resin layer to 500 nm or less, it is possible to further suppress unevenness and streaks when applying the resin layer without increasing the manufacturing cost, thereby maintaining the quality of the laminated film.
[0191] The thickness of the resin layer can be measured using a cross-sectional image obtained by a transmission electron microscope (TEM), and the details are described below. In addition, for the laminated film of the present invention, the method for adjusting the thickness of the resin layer is not particularly limited and can be appropriately selected from known methods, such as a method for adjusting the solid content concentration in the resin composition.
[0192] In general, a solar cell is formed by laminating a transparent substrate such as glass and a resin sheet called a backplane (back protection sheet) on a component formed by sealing a power generation element with a transparent sealing material, and the laminated film of the present invention is suitable for a solar cell module having a structure in which the sealing material is directly laminated. In addition, it is preferably used for a solar cell module having two sealing materials (sealing materials 1, 2) and sequentially having the above-mentioned sealing material 1, a solar cell unit, the above-mentioned sealing material 2 and the above-mentioned laminated film.
[0193] Solar cells use power generation elements to convert sunlight energy that enters through a transparent substrate into electrical energy. The resulting electrical energy is taken out through leads connected to the power generation elements and used in various electrical devices. By improving the heat insulation of the laminated polyester film, the temperature rise of the solar cell caused by direct sunlight and reflected light from the ground surface is reduced, thereby suppressing the degradation of the solar cell caused by heat, leading to improved power generation efficiency.
[0194] The laminated film of the present invention comprises an interlayer and glass, and is suitable for use in a glass structure in which the laminated film and the interlayer are adjacent. For example, a glass laminate in which the laminated film of the present invention is laminated on one surface of a glass using an interlayer, a laminated glass in which a laminated film is inserted between two glasses and two interlayers, etc. can be cited. In addition, it is preferably used in a glass structure (laminated glass) having two glasses (glass 1, 2) and two interlayers (interlayer 1, 2) and having glass 1, interlayer 1, laminated film, interlayer 2 and glass 2 in sequence.
[0195] The glass used in the glass structure of the present invention is not particularly limited, and commonly used transparent flat glass can be used, such as transparent glass, float flat glass, polished flat glass, patterned glass, wired flat glass, wired flat glass, infrared absorbing flat glass, infrared reflecting flat glass, green glass, etc.
[0196] In addition, as the intermediate layer used in the glass structure of the present invention, there is no particular limitation, and examples thereof include resins such as vinyl acetate resins, vinyl chloride-vinyl acetate copolymers, ethylene-vinyl acetate copolymers, polyvinyl alcohol, polyvinyl butyral, polyvinyl acetal, polyvinyl ether, nitrile rubber, styrene-butadiene rubber, natural rubber, chloroprene rubber, polyamide, epoxy resin, polyurethane, acrylic resin, cellulose, polyvinyl chloride, polyacrylate, and polyisobutylene. In addition, adhesion regulators, plasticizers, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, lubricants, colorants, crosslinking agents, etc. can be added to these intermediate layers. By providing an intermediate layer, the adhesion between glass and laminated film, the design, durability, weather resistance, and impact resistance of laminated glass can be improved.
[0197] In addition, the intermediate layer used in the glass structure of the present invention may contain a component that improves design. As a component that improves design, there is a colorant, and examples thereof include azo pigments, polycyclic pigments, lake pigments, nitro pigments, nitroso pigments, aniline black, alkaline blue, phthalocyanine pigments, cyanine pigments, azo dyes, anthraquinone dyes, quinophthalone dyes, methine dyes, condensed polycyclic dyes, reactive dyes, cationic dyes, lanthanum hexaboride, indium tin oxide, antimony tin oxide, cesium tungsten oxide, and the like.
[0198] As the molding method of the intermediate layer, there are extrusion lamination, hot melt lamination, heat lamination, pressurized lamination, vacuum lamination, autoclave lamination and the like. Extrusion lamination refers to a method in which a laminated film and an intermediate layer in a molten state are extruded from a die head into a film shape and laminated on a glass, and the molded product is formed by passing the molded product between two rollers. Hot melt lamination refers to a molding method in which an intermediate layer melted by heat is coated on a laminated film or glass, and the laminated film and the glass are laminated. Heat lamination refers to a molding method in which a laminated film, an intermediate layer and a glass are laminated while being heated with a heating roller. Pressurized lamination refers to a molding method in which a laminated film, an intermediate layer and a glass are heated and laminated with a press. Vacuum lamination refers to a molding method in which a laminated film, an intermediate layer and a glass are heated, and then the inside of the device is made into a vacuum state, and then pressed and laminated. Autoclave lamination refers to a molding method in which a laminated film, an intermediate layer and a glass are heated, and then the inside of the device is pressurized with gas or the like to laminate.
[0199] The glass structure of the present invention preferably satisfies 3≤d1 / d2≤100 when the thickness of the intermediate layer 1 is set to d1 and the thickness of the intermediate layer 2 is set to d2. By setting the thickness of the two intermediate layers to a preferred range, it is preferred that the double image of the projected image can be suppressed when used in a projection component such as a projection image display component and a head-up display (HUD) having a reflection characteristic of a P wave. In addition, the thickness of the intermediate layer is preferably 10 μm to 1 mm.
[0200] The glass structure of the present invention preferably satisfies 1.5≤d3 / d4≤10 when the thickness of glass 1 is set to d3 and the thickness of glass 2 is set to d4. By setting the thickness of the two sheets of glass to an appropriate range, it is preferred that the double image of the projected image can be suppressed when used in a projection component such as a projection image display component and a head-up display (HUD) having a reflection characteristic of a P wave. The thickness of the glass is preferably 0.5 mm to 5.0 mm.
[0201] The glass structure using the laminated film thus obtained has excellent heat insulation performance on the inside and excellent transparency, and is therefore particularly suitable for heat-insulating glass used in automobiles, building windows, and the like. In addition, when used in projection components such as projection image display components and head-up displays (HUDs) having a P-wave reflection characteristic, it is a preferred display device having high display performance of the projected image and good visibility of the surrounding scenery. That is, the automobile and building window of the present invention include the glass structure of the present invention.
[0202] Example
[0203] Hereinafter, the laminated film of the present invention will be specifically described using examples. However, the laminated film of the present invention is not limited to the above-described embodiments.
[0204] [Methods for measuring physical properties and evaluating effects]
[0205] The evaluation methods of the physical property values and the evaluation methods of the effects are as follows.
[0206] (1) Identification of substrate
[0207] The composition of the resin constituting the substrate is confirmed by the following method. First, Fourier transform infrared spectroscopy (FT-IR or ATR) is used to confirm the presence or absence of peaks originating from the bonds between the atoms in the resin structure. In addition, proton nuclear magnetic resonance spectroscopy ( 1 H-NMR) to confirm the chemical shift position of the position of the hydrogen atoms possessed by the resin structure and the proton absorption line area derived from the number of hydrogen atoms. These results are combined for comprehensive confirmation to identify the substrate. In addition, the mass peak can also be confirmed by gas chromatography-mass spectrometry (GC-MS) as needed. It should be noted that the above analysis is performed by cutting a sample from the laminated film with a knife.
[0208] (2) Thickness of the resin layer
[0209] The laminated film is dyed with RuO4 and / or OsO4. Next, the laminated film is frozen and cut along the film thickness direction to obtain 10 ultra-thin section samples for cross-sectional observation of the resin layer. The cross-section of each sample is observed at 10,000 to 1,000,000 times using a TEM (transmission electron microscope: H7100FA manufactured by Hitachi, Ltd.) to obtain a cross-sectional photograph. Using the length measurement function of the microscope, the thickness of the resin layer of each sample is measured from the cross-sectional photograph, and the measured values of the resin layer thickness of the 10 samples are averaged as the thickness of the resin layer of the laminated film.
[0210] (3) Derivation of Xs, Xc, Xb, XO, and XOs of the resin layer
[0211] First, the composition distribution in the depth direction was analyzed from the surface side of the resin layer of the laminate film using the analytical method GCIB-TOF-SIMS (GCIB: gas cluster ion beam, TOF-SIMS: time-of-flight secondary ion mass spectrometry). The measurement conditions were as follows.
[0212] <Sputtering conditions>
[0213] Ion source: Argon gas cluster ion beam (Ar-GCIB)
[0214] <Testing conditions>
[0215] Primary ion: Bi 3++ (25kV)
[0216] Secondary ion polarity: positive
[0217] Mass range: m / z 0~1500
[0218] Measuring range: 300×300μm 2
[0219] Determination of vacuum degree: 4×10 -7 Below Pa
[0220] Through the measurement under the above conditions, a curve of the absolute intensity of positive secondary ions of each component in GCIB-TOF-SIMS relative to the sputtering time is obtained. Among them, in the curve of the absolute intensity of positive secondary ions equivalent to the main component of the substrate identified in (1), an approximate straight line of 100 consecutive points is calculated, and the average value of the 100 points located on the innermost layer side (substrate side) among the 100 points with a slope of less than ±15 is taken as the "substrate absolute intensity". The 1 / 2 intensity sputtering time as the "substrate absolute intensity" calculated above is derived and designated as the "1 / 2 intensity sputtering time", and this point is defined as the boundary between the resin layer and the substrate. That is, it means that the sputtering time from 0 to 1 / 2 intensity sputtering time represents the component distribution of the resin layer, and the 1 / 2 intensity sputtering time and thereafter represents the component distribution of the substrate.
[0221] Next, a method for converting the sputtering time in the curve of the absolute intensity of positive secondary ions of GCIB-TOF-SIMS into the thickness of the resin layer is described. The value obtained by dividing the resin layer thickness obtained in the measurement of (2) above by the 1 / 2 intensity sputtering time calculated above is used as the etching rate, and based on the etching rate, the sputtering time is converted into the thickness of the resin layer, thereby obtaining a curve of the absolute intensity of positive secondary ions of each component in GCIB-TOF-SIMS relative to the thickness of the resin layer.
[0222] Next, a method for converting the absolute intensity of positive secondary ions of each component into the standardized intensity of positive secondary ions of each component is described. The absolute intensity of the substrate calculated using the above method is standardized to 1, and the standardized intensity of positive secondary ions of each component is obtained from the absolute intensity of positive secondary ions of each component. Among the standardized intensities of positive secondary ions of each component, the standardized intensity at a position 20% of the thickness from the surface of the resin layer is set to Xs, the standardized intensity at a position 50% of the thickness from the surface of the resin layer is set to Xc, and the standardized intensity at a position 80% of the thickness from the surface of the resin layer is set to Xb. In addition, the standardized intensity of the oxazoline compound on the surface of the resin layer is set to XO, and the standardized intensity at a position 20% of the thickness from the surface of the resin layer is set to XOs.
[0223] It should be noted that examples of the positive secondary ions of the acrylic resin include 69 C4H5O + As the positive secondary ions of the polyester resin, for example, 104C7H4O + As the positive secondary ions of the polyurethane resin, for example, 122 C7H8NO + As the positive secondary ion of the oxazoline compound or the chemical structure derived from the oxazoline compound, for example, 112 C6H 10 NO + Etc. Here, “the position at which the thickness is 20% from the surface of the resin layer” refers to the position at which the thickness is closest to 20 / 100 of the thickness of the resin layer when viewed from the surface of the resin layer. Similarly, “the position at which the thickness is 50% from the surface of the resin layer” refers to the position at which the thickness is closest to 50 / 100 of the thickness of the resin layer when viewed from the surface of the resin layer, “the position at which the thickness is 80% from the surface of the resin layer” refers to the position at which the thickness is closest to 80 / 100 of the thickness of the resin layer when viewed from the surface of the resin layer, and “the surface of the resin layer” refers to the surface of the resin layer.
[0224] (4) AFM elastic modulus of the resin layer
[0225] The measurement was performed using NanoScopeV manufactured by Bruker AXS Co., Ltd. The measurement was performed in accordance with the attached "Measurement Procedure PeakForce QNM", and the measurement conditions are as follows. The measurement at 25°C was performed using a sample that had been left standing in a room adjusted to 25°C for 24 hours, and the measurement at -20°C was performed immediately after taking out a sample that had been left standing in a portable freezer adjusted to -20°C for 24 hours. The measurements were all carried out at room temperature of 23°C and a relative humidity of 65%. The measurement was performed 10 times, and the average value was used as the AFM elastic modulus (P(25), P(-20)) of the resin layer at each temperature, and ΔP(P(-20)-P(25)) and the elastic modulus ratio P' (P(-20) / P(25)) were calculated.
[0226] Probe: RTESPA-300
[0227] ScanSize: 1nm
[0228] ScanRate: 1Hz
[0229] PeakForce Setpoint: 40.00mN.
[0230] (5) Melting point, crystallization temperature, melting enthalpy, micro-endothermic peak, glass transition temperature of the resin layer
[0231] The sample was collected by cutting out 5 mg with a cutter or a knife, and measured and calculated according to JIS-K-7122 (1987) using a differential scanning calorimeter (DSC) (Robot DSC-RDC220 manufactured by Seiko Instruments). More specifically, the sample was heated from 25°C to 300°C at 5°C / min, and the peak located near the melting point and on the low temperature side lower than the melting point at this time was taken as a small endothermic peak, and the integral value from the baseline within the range of ±20°C of the melting point was taken as the melting enthalpy. In addition, the melting point here refers to a point where the difference from the baseline of the DSC graph is extremely small. The crystallization temperature refers to a point where the difference from the baseline of the DSC graph at the exothermic peak on the low temperature side lower than the melting point is extremely large. The small endothermic peak was observed in the first run of the DSC, and was not observed in the second run where the thermal history was eliminated by heating to above the melting point once, so it can be confirmed by comparing the two DSC graphs. The glass transition temperature of the resin layer is also measured and calculated according to JIS-K-7122 (1987). More specifically, the temperature of the point where a straight line equidistant from the baseline on the low temperature side and the extended straight line on the high temperature side in the longitudinal direction intersects with the curve of the step-shaped change portion of the glass transition is taken as the glass transition temperature.
[0232] (6) Water drop contact angle
[0233] The water drop contact angle is measured according to the sessile drop method described in JIS R3257:1999. First, the laminated film is placed in an atmosphere of room temperature 23°C and relative humidity 65% for 24 hours. Then, under the same atmosphere, the contact angle of pure water at 5 points is measured by the 2 / θ method using a CA-D contact angle meter (manufactured by Kyowa Interface Science Co., Ltd.) on the surface side of the resin layer of the laminated film. The measurement is carried out within 10 seconds after the pure water contacts the resin layer. The measured values of 3 points excluding the maximum and minimum values of the 5 measured values are averaged, and the value twice the measured value is taken as the water drop contact angle.
[0234] (7) Confirmation of the structure of the resin layer
[0235] The structure of the resin layer is confirmed by the following method. In order to determine the polyurethane structure and the structure of the following formula (1) to (5), the weight peaks of the aliphatic isocyanate compound and the polyol compound that are cut off at the urethane bond part are confirmed by gas chromatography-mass spectrometry (GC-MS). The presence or absence of weight peaks originating from the structure of the following formula (1) to (5) is also confirmed. Next, Fourier transform infrared spectroscopy (FT-IR) is used to confirm the presence or absence of peaks originating from the isocyanate compound component and the polyol compound, as well as the bonds between the atoms possessed by the structures of the following formula (1) to (5). In addition, proton nuclear magnetic resonance spectroscopy ( 1H-NMR) confirms the chemical shift position of the position of the hydrogen atoms and the proton absorption line area of the number of hydrogen atoms in the structures of isocyanate compounds, polyol compounds, oxazoline compounds and the following formulas (1) to (5). These results are comprehensively confirmed to confirm the structure of the resin. It should be noted that the above analysis is carried out on the sample obtained by cutting the resin layer with a knife. The same method as the above example is also used to confirm the chemical structure of acrylic modified polyester resin, oxazoline compound or oxazoline compound, and the structure of melamine compound.
[0236]
[0237] (8) Preparation of samples used in the peel strength test of EVA and PVB (25°C, -20°C)
[0238] The laminated film was cut into a size of 10 cm in length and 3 cm in width, and EVA ("Sonaru" (registered trademark) DC3203 manufactured by Mitsubishi Chemical Corporation) and PVB ("Esleck Film" HI manufactured by Sekisui Chemical Co., Ltd.) were cut into a size of 40 cm in length and 1 cm in width. EVA and PVB were overlapped in the center of the width direction of the laminated film with the long sides parallel to each other, and the exposed part was sandwiched with a protective film ("Selapil" (registered trademark) #25WZ (RX) manufactured by Toray Film Processing Co., Ltd.). It was preheated in a hot air oven heated to 140°C for 1 minute, and laminated at a speed of 300 mm / min using a laminator heated to 140°C (MRK-600 manufactured by MCK Co., Ltd.), thereby obtaining a sample.
[0239] (9) EVA and PVB peel strength test (25℃, -20℃)
[0240] The measurement was performed using the adhesion-film peeling analyzer VPA-2 manufactured by Kyowa Interface Science Co., Ltd. according to the following steps. First, the sample prepared in (8) was fixed to the measuring unit together with the attached stainless steel plate with tape, and the EVA and PVB parts protruding from the laminated film part of the sample were fixed to the sample fixing plate. Then, the peeling force was measured under the following measurement conditions, and the average value of the peeling force in the 20mm interval where the peeling force was most uniform within the measurement distance of 100mm was calculated. The same measurement was performed 5 times for each sample, and the average value of the 5 times was taken as the peeling force (N / mm), and evaluated according to the following evaluation criteria (◎ and ○ were considered as good results). It should be noted that the peeling force test at 25°C was performed on samples that were left to stand for 24 hours in a room adjusted to 25°C. The peeling force test at -20°C was performed immediately after the sample and the attached stainless steel plate were left to stand in a portable freezer adjusted to -20°C for 24 hours and taken out.
[0241] <Measurement conditions>
[0242] Force sensor: 100N
[0243] Peeling speed: 300mm / min
[0244] Peeling angle: 180°
[0245] Sample width (bandwidth): 10mm
[0246] Measuring distance: 100mm.
[0247] <Evaluation Criteria>
[0248] ◎: higher than 1.0N / mm
[0249] ○: 0.8 N / mm or more and 1.0 N / mm or less
[0250] ×: less than 0.8 N / mm.
[0251] (10) Layer thickness, number of layers, and layer structure
[0252] For the sample obtained by cutting out a cross section parallel to the thickness direction (cross section in the thickness direction) using a microtome, the layer structure of the film is confirmed by observation using a transmission electron microscope (TEM). More specifically, a transmission electron microscope H-7100FA (manufactured by Hitachi, Ltd.) is used to magnify the cross section in the thickness direction of the film by 10,000 to 40,000 times under an accelerating voltage of 75 kV for observation and photographing. The layer structure is confirmed by the obtained image and the scale function of the TEM, and the thickness of each layer is measured. It should be noted that, depending on the situation, in order to obtain high contrast, a well-known staining technique using RuO4 or OsO4, etc. can be used. It should be noted that the thickness direction refers to the direction perpendicular to the film surface.
[0253] (11) Adhesion
[0254] Two films were cut out according to a width of 30 mm and a length of 60 mm, and the surfaces with the resin layer were overlapped by 40 mm in the length direction. A weight of 30 mm in width and 40 mm in length and 6 kg was placed on the overlapped portion, and the film was treated for 168 hours in an atmosphere of 60°C and 95% RH. The laminated film after treatment was peeled off and evaluated according to the following criteria (◎, ○, and △ were considered good results). It should be noted that in the evaluation, the resistance during peeling was evaluated by sensory evaluation by holding the two films by hand, and the observation of whitening and peeling was performed visually.
[0255] <Evaluation Criteria>
[0256] ◎: There is no resistance during peeling, and the resin layer surface after peeling does not whiten or peel.
[0257] ○: There was some resistance during peeling, but the surface of the resin layer after peeling did not whiten or peel.
[0258] △: There was resistance during peeling, but the surface of the resin layer after peeling did not whiten or peel.
[0259] ×: There was resistance during peeling, and whitening and peeling were observed on the surface of the resin layer after peeling.
[0260] (12) Production of laminated glass
[0261] Laminator 0303S manufactured by Nisshinbo Co., Ltd. was used, and transparent flat glass, an intermediate layer, a film of an embodiment or a comparative example, an intermediate layer, and a transparent flat glass were stacked in this order, and pressed for 30 minutes at a temperature of 140°C and 1.5 MPa, thereby producing laminated glass. The transparent flat glass was 100 mm wide by 100 mm long, and the thickness was as described in Tables 3 and 4. A PVB film was used as an intermediate layer, and the thickness was as described in Tables 3 and 4.
[0262] (13) Preparation of glass laminate
[0263] LAMINATOR 0303S manufactured by Nisshinbo Co., Ltd. was used, and transparent flat glass, an intermediate layer, and the films of Examples 38 to 41 were stacked in this order, and pressed at a temperature of 140° C. and 1.5 MPa for 30 minutes to produce a glass laminate. The transparent flat glass had a width of 100 mm and a length of 100 mm, and the thickness was as described in Tables 3 and 4. A PVB film was used as the intermediate layer, and the thickness was as described in Tables 3 and 4.
[0264] (14) Laminated glass appearance (concave and convex)
[0265] The laminated glass prepared in (12) was placed under a fluorescent lamp, and the evaluation portion was visually evaluated at angles of 20°, 50°, and 70° relative to the normal direction of the evaluation portion. The evaluation criteria are as follows.
[0266] ○: No irregularities are seen or irregularities are slightly seen.
[0267] ×: Concavities and convexities are visible.
[0268] (15) Reflectivity
[0269] For samples cut out at 5 cm x 5 cm, reflectivity was measured using the basic configuration of an integrating sphere attached to a spectrophotometer (U-4100 Spectrophotomater) manufactured by Hitachi, Ltd. In this measurement, the measurement was performed using the alumina sub-white plate attached to the device as a reference. In the reflectivity measurement, the length direction of the sample was set to the up-down direction and set behind the integrating sphere, and the surface of the resin layer of the laminated film was set as the incident surface. The reflectivity was measured under the following conditions, and the average reflectivity in the wavelength bands of 400 nm to 700 nm and 850 nm to 1200 nm was calculated.
[0270] <Measurement conditions>
[0271] Slit: 2nm (visible light) / automatic control (infrared)
[0272] Gain: 2
[0273] Scanning speed: 600nm / min
[0274] Starting wavelength: 2600nm
[0275] End wavelength: 240nm
[0276] Sampling interval: 1nm
[0277] Angle of incidence: 10°.
[0278] (16) Thermal insulation
[0279] The total energy transmittance (Tts) of the laminated glass produced by (12) was measured in accordance with ISO 13837:2008 "Road vehicles - Safety glazing materials - Determination of solar transmittance". The total energy transmittance (Tts) of the laminated glass was evaluated according to the following 4 levels.
[0280] ◎: The total energy transmittance (Tts) through the laminated glass is 50% or less.
[0281] ○: The total energy transmittance (Tts) through the laminated glass is greater than 50% and less than 60%.
[0282] △: The total energy transmittance (Tts) through the laminated glass is greater than 60% and less than 70%.
[0283] ×: The total energy transmittance (Tts) through the laminated glass is 70% or more.
[0284] (17) Transmittance
[0285] The average transmittance was determined by measuring the surface of the resin layer of the laminated film under the following conditions using a standard configuration (solid measurement system) of a spectrophotometer (U-4100 Spectrophotomater) manufactured by Hitachi, Ltd., with the surface being the incident surface, to determine the average transmittance.
[0286] <Measurement conditions>
[0287] Slit: 2nm (visible light) / automatic control (infrared)
[0288] Gain: 2
[0289] Scanning speed: 600nm / min
[0290] Starting wavelength: 700nm
[0291] End wavelength: 400nm
[0292] Sampling interval: 1nm
[0293] Angle of incidence: 0°.
[0294] (18) Determination of R20, R40, and R70
[0295] The spectrophotometer (U-4100 Spectrophotomater) manufactured by Hitachi, Ltd. was installed with an angle-variable reflection unit and a Glan Taylor polarizer, and the resin layer surface of the laminated film was used as the incident surface. The reflectivity of the P wave was measured at 1 nm scale within the wavelength range of 400 to 700 nm at incident angles θ = 20°, 40°, and 70°. R20, R40, and R70 were calculated from the obtained reflectivity as the average reflectivity of the P wave within the wavelength range of 400 to 700 nm at incident angles of 20°, 40°, and 70°.
[0296] (19) Display
[0297] For the laminated glass produced in (12) and the glass laminate produced in (13), when a P-wave light source is used at an incident angle of 70° to reflect a white straight line onto a black background, a sensory evaluation is performed on the visibility of the white straight line, and the visual visibility is evaluated according to the following three levels. It should be noted that in the case of laminated glass, the thinner of the two intermediate layers is regarded as d2, and the thinner of the two glasses is regarded as d4, and light is incident from the intermediate layer side with a thickness of d2 and the glass side with a thickness of d4. In addition. In the case of a glass laminate, light is incident from the laminated film side. It should be noted that in laminated glass, when the thickness of the two intermediate layers and the two glasses is the same, the results are the same when measured from either side.
[0298] ◎: Can be identified by visual inspection.
[0299] ○: Can be visually identified, but the brightness is slightly poor.
[0300] ×: Cannot be identified by visual inspection.
[0301] (20) Ghosting
[0302] For the laminated glass produced in (12) and the glass laminate produced in (13), when a P-wave light source was used at an incident angle of 70° to reflect white straight lines onto a black matrix, the number of white straight lines and the appearance were visually evaluated according to the following three levels.
[0303] ◎: A straight line is observed slightly blurrily.
[0304] 〇: Two straight lines are seen, but they are very close to each other.
[0305] ×: See two straight lines that are far apart.
[0306] (21) Average change rate of shrinkage
[0307] The measurement was performed using a heat-applied-strain measuring device (TMA / SS6000) manufactured by Seiko Instruments under the following measurement conditions. For the sample, cut in any direction in the plane parallel to the film surface and in each direction rotated at 5° intervals to 180° in the plane direction parallel to the film surface. For each data, the shrinkage rate S(T) at each temperature was calculated using formula (9) in such a way that at least one data point was obtained every 1°C, and the shrinkage rate was plotted on the vertical axis and the temperature on the horizontal axis to obtain a heat shrinkage curve. The measurement was performed 3 times in each direction, and the direction in which S(150) was the largest was taken as the X direction.
[0308] <Measurement conditions>
[0309] Sample size: width 4mm, length 15mm
[0310] Heating range: 25~200℃
[0311] Heating rate: 10℃ / min
[0312] Test load: 19.8N
[0313] Temperature 23℃, relative humidity 65%, atmosphere
[0314] S(T)=(L(25)-L(T))×100 / L(25) (9)
[0315] Here, L(T) is the length of the sample at T°C.
[0316] From the obtained shrinkage ratio S(T), the average change ratio of the shrinkage ratio at 100°C to 150°C (average change ratio of the shrinkage ratio) was calculated using formula (10).
[0317] Average change rate of shrinkage rate = |S(150)-S(100)| / (150-100) (10)
[0318] [Resin used in film]
[0319] Resin 1: A polyethylene terephthalate resin showing crystallinity with a glass transition temperature of 78° C., a melting point of 254° C., a crystallization temperature of 180° C., and a melting enthalpy of 40 J / g.
[0320] Resin 2: A non-crystalline polyethylene terephthalate resin having a glass transition temperature of 80°C and copolymerized with 33 mol % of cyclohexanedimethanol.
[0321] Resin 3: A non-crystalline polyethylene terephthalate resin blend prepared by blending a polyethylene terephthalate resin having a glass transition temperature of 80° C. and copolymerized with 29 mol % of spiroglycol and 21 mol % of cyclohexanedicarboxylic acid and resin 1 at a ratio of 70:30.
[0322] Resin 4: A non-crystalline copolymerized polynaphthalate resin having a glass transition temperature of 81° C., comprising 70 mol % of 2,6-naphthalene dicarboxylic acid and 30 mol % of isophthalic acid as dicarboxylic acid components, and 98 mol % of ethylene glycol and 2 mol % of polyethylene glycol having a molecular weight of 400 as diol components.
[0323] (Example 1)
[0324] Coating solution containing acrylic modified polyester resin:
[0325] 50 parts by mass of terephthalic acid, 50 parts by mass of isophthalic acid, 50 parts by mass of ethylene glycol, 30 parts by mass of neopentyl glycol, 0.3 parts by mass of antimony trioxide and 0.3 parts by mass of zinc acetate as polymerization catalysts were added to a reactor purged with nitrogen. Then, a polymerization reaction was carried out for 12 hours under normal pressure and a temperature of 190 to 220° C. while removing water to obtain a polyester diol. Next, 5 parts by mass of sodium 5-sulfonate of isophthalic acid and xylene as a solvent were added to the obtained polyester diol, and the mixture was added to a reactor. The xylene was removed by distillation under reduced pressure conditions of 0.2 mmHg and 260° C., and polymerization was carried out for 3 hours to obtain a polyester resin component. The polyester resin component was dissolved in ammonia water and water containing butyl cellulose to obtain an aqueous dispersion containing the polyester resin component. Next, 50 parts by weight of methyl methacrylate and 10 parts by weight of methacrylamide were added to the aqueous dispersion containing the polyester resin component so as to achieve a mass ratio of acrylic resin component / polyester resin component of 50 / 50. Furthermore, 5 parts by weight of benzoyl peroxide was added as a polymerization initiator, and a polymerization reaction was carried out at 70 to 80° C. for 3 hours in a reactor purged with nitrogen to obtain a coating liquid containing an acrylic modified polyester resin.
[0326] Coating liquid containing polyurethane resin:
[0327] In a four-necked flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, and a stirrer, 70 parts by mass of 1,6-hexane diisocyanate as an aliphatic polyisocyanate compound, 30 parts by mass of polyisobutylene glycol as a polyol compound, 60 parts by mass of acetonitrile as a solvent, and 30 parts by mass of N-methylpyrrolidone were added. Then, under a nitrogen atmosphere, the temperature of the reaction liquid was adjusted to 75-78°C, 0.06 parts by mass of stannous octoate as a reaction catalyst was added, and it was reacted for 7 hours. Then, it was cooled to 30°C to obtain an aliphatic polyurethane resin with an isocyanate group at the end. Then, water was added to a reaction container equipped with a homogenizer capable of high-speed stirring and adjusted to 25°C, and while stirring and mixing at 2000 rpm, an aliphatic polyurethane resin with an isocyanate group at the end was added to disperse it in water. Then, a portion of acetonitrile and water was removed under reduced pressure, thereby preparing a coating liquid containing a polyurethane resin (referred to as polyurethane 1 in Table 1-1).
[0328] Coating solution containing oxazoline compound:
[0329] In a flask equipped with a reflux condenser, a nitrogen inlet tube, a thermometer, a stirrer, and a dropping funnel, 782.4 parts by mass of deionized water and 128 parts by mass of a surfactant (a 15% aqueous solution of "Hytenol" (registered trademark) N-08 manufactured by Daiichi Kogyo Seiyaku) were added, the pH was adjusted to 9 with aqueous ammonia (28%), and the mixture was heated to 70°C while nitrogen was circulated. 64 parts by mass of a 5% aqueous solution of potassium persulfate was injected therein, and then a monomer mixture of 320 parts by mass of methyl methacrylate, 160 parts by mass of ethyl acrylate, 32 parts by mass of styrene, and 128 parts by mass of 2-isopropenyl-2-oxazoline, which had been mixed and stirred in another flask in advance, was added dropwise over 3 hours. During the reaction, the temperature of the reaction liquid was maintained at 70°C under a nitrogen atmosphere. After the addition was completed, the temperature was maintained at the same temperature for 2 hours, and then the temperature of the reaction liquid was raised to 80°C, and stirring was continued for 1 hour to terminate the reaction. The mixture was then cooled and diluted in a mixed solvent of propylene glycol monomethyl ether and water (20 / 80 (mass ratio)) to prepare a coating liquid containing an oxazoline compound.
[0330] Resin composition:
[0331] The obtained coating liquid containing an acrylic modified polyester resin, a coating liquid containing a polyurethane resin, a coating liquid containing an oxazoline compound, and a melamine compound "Nikalak" (registered trademark) MW-035 (manufactured by Sanwa Chemical) were mixed so that the solid content mass ratio was acrylic modified polyester resin / polyurethane resin / oxazoline compound / melamine compound = 90 / 10 / 60 / 10, and the total solid content was adjusted to 10% by mass to obtain a coating liquid A. In order to impart slipperiness to the surface of the resin layer, 2 parts by mass of silica particles ("Snotex" (registered trademark) MP-2040 manufactured by Nissan Chemical Industries, Ltd.) having a number average particle diameter of 170 nm were added as inorganic particles relative to 100 parts by mass of the total solid content of the coating liquid A. In order to improve the coating property of the resin composition on the polyester film, a fluorine-based surfactant ("Pluscode" (registered trademark) RY-2 manufactured by Huying Chemical (Strain) was added in an amount of 0.03 parts by mass relative to 100 parts by mass of the coating liquid A. Then, the resin composition was diluted with a mixed solvent of isopropyl alcohol and water (20 / 80 (mass ratio)) in an amount of 5% by mass of the solid content.
[0332] Laminated film:
[0333] Resin 1 is used as a crystalline thermoplastic resin constituting layer A (hereinafter also referred to as resin A), and resin 2 is used as a thermoplastic resin constituting layer B (hereinafter also referred to as resin B). Resins A and B are melted at 280°C using different extruders, and foreign matter is removed through 5 FSS-type leaf disk filters. Then, while metering with a gear pump in a manner such that the discharge ratio becomes resin A / resin B=1 / 1.07, the two are merged using a 401-layer feed head, and resin A and resin B are alternately laminated in a total of 401 layers in the thickness direction in such a manner that the outermost layers on both sides become resin A. At this time, the layer thickness of layer A and layer B is designed in such a way that the reflectivity spectrum in the wavelength range of 380nm to 780nm becomes flat. Next, the obtained molten laminate is supplied to a T-die, and after being formed into a sheet, an electrostatic voltage of 8kV is applied by an electric wire, and it is quenched and solidified on a casting drum whose surface temperature is maintained at 25°C to obtain an unstretched film. The unstretched film was longitudinally stretched using the roller circumferential speed difference at a temperature of 90°C and a magnification of 3.5 times, and then temporarily cooled to obtain a uniaxially stretched film. Next, the two sides of the uniaxially stretched film were subjected to corona discharge treatment in the air, and the resin composition was applied to the treated surface using a rod coater in a manner such that the coating thickness was about 6 μm. The two ends in the width direction were then clamped with a clamp, and the uniaxially stretched film was introduced into a tenter, and after being transversely stretched at a temperature of 110°C and a magnification of 4.3 times, it was heat treated at 210°C, and then 1.6% of the width direction was relaxed to obtain a laminated film with a thickness of 80 μm (referred to as laminated film 1 in Table 1-3). The obtained laminated film has a flat reflectivity distribution that reflects infrared rays with a wavelength of 850 to 1200 nm and has almost no reflection in the visible light region with a wavelength of 400 to 700 nm. The evaluation results of the obtained laminated films are shown in Tables 1-1, 1-2, and 1-3, and the properties of the laminated film 1 are shown in Table 2.
[0334] (Example 2)
[0335] A laminated film was prepared under the same conditions as in Example 1 except that the acrylic resin as the acrylic modified polyester resin was changed to 40 parts by mass of methyl methacrylate and 10 parts by mass of 2-hydroxyethyl methacrylate, for a total of 50 parts by mass. The composition of the resin composition and the evaluation results of the obtained laminated film are shown in Tables 1-1, 1-2, and 1-3.
[0336] (Example 3)
[0337] A laminated film was prepared under the same conditions as in Example 1 except that the acrylic resin as the acrylic modified polyester resin was changed to 40 parts by mass of methyl methacrylate and 10 parts by mass of ethylene glycol methacrylate, for a total of 50 parts by mass. The composition of the resin composition and the evaluation results of the obtained laminated film are shown in Tables 1-1, 1-2, and 1-3.
[0338] (Example 4)
[0339] A laminated film was prepared under the same conditions as in Example 1 except that the acrylic resin as the acrylic modified polyester resin was changed to 40 parts by mass of methyl methacrylate and 10 parts by mass of triethylamine acrylate, for a total of 50 parts by mass. The composition of the resin composition and the evaluation results of the obtained laminated film are shown in Tables 1-1, 1-2, and 1-3.
[0340] (Example 5)
[0341] A laminated film was prepared under the same conditions as in Example 1 except that the acrylic resin as the acrylic modified polyester resin was changed to 40 parts by mass of methyl methacrylate and 10 parts by mass of glycidyl acrylate, for a total of 50 parts by mass. The composition of the resin composition and the evaluation results of the obtained laminated film are shown in Tables 1-1, 1-2, and 1-3.
[0342] (Examples 6, 9 to 20, 22 to 28, Comparative Examples 1 to 6)
[0343] A laminated film was prepared under the same conditions as in Example 1 except that the composition of the resin composition was changed as shown in Table 1-1. The evaluation results of the obtained laminated films are shown in Table 1-2 and Table 1-3. It should be noted that the carbodiimide compound used was "Carbodiimide" (registered trademark) V-04 (manufactured by Nisshinbo Chemical Co., Ltd.).
[0344] (Examples 7 and 8)
[0345] The acrylic resin as the acrylic modified polyester resin was changed to 50 parts by mass of methyl methacrylate, and the composition of the resin composition was changed as shown in Table 1-1. A laminated film was prepared under the same conditions as in Example 1. The evaluation results of the obtained laminated film are shown in Table 1-2 and Table 1-3. It should be noted that the polyester-polyurethane copolymer was obtained by the following steps.
[0346] Coating solution containing polyester-polyurethane copolymer:
[0347] 100 parts by mass of polyester polyol (adipic acid / 3-methyl-1,5-pentanediol), 3.0 parts by mass of trimethylolpropane, 10 parts by mass of dimethylolpropionic acid, and 58 parts by mass of isophorone diisocyanate were reacted in methyl ethyl ketone (MEK) to obtain a polyester-polyurethane copolymer. 7.5 parts by mass of triethylamine was mixed therein and added to water to disperse the polyester-polyurethane copolymer in water, and the chain was extended with ethylenediamine to obtain a dispersion. Methyl ethyl ketone was removed by distillation to obtain a coating solution containing a polyester-polyurethane copolymer containing 30% by mass of non-volatile components.
[0348] (Example 21)
[0349] A coating liquid containing a polyurethane resin (abbreviated as polyurethane 2 in Table 1-1) was prepared by the same method as in Example 1 except that isophorone diisocyanate was used as the aliphatic polyisocyanate compound of the coating liquid containing a polyurethane resin, and a film was prepared under the same conditions as in Example 1 except that the composition of the resin composition was changed as shown in Table 1-1. The evaluation results of the obtained films are shown in Tables 1-2 and 1-3.
[0350] (Comparative Example 7)
[0351] When the composition of the resin composition was set to compound A: methyl methacrylate 70 mol% / ethyl acrylate 20 mol% / 2-hydroxyethyl methacrylate 10 mol%, compound B: terephthalic acid 32 mol% / isophthalic acid 12 mol% / 5-sodium sulfoisophthalate 6 mol% / ethylene glycol 46 mol% / diethylene glycol 4 mol%, compound C: 1,3-bis(N,N-diglycidylamino)cyclohexane, and compound D: polyoxyethylene (n=7) lauryl ether, the weight percentages of each were mixed in water at compound A:compound B:compound C:compound D=43:43:4:10 to make the solid content concentration 3 mass%, and a laminated film was produced under the same conditions as in Example 1. The composition of the resin composition and the evaluation results of the obtained laminated film are shown in Tables 1-1, 1-2, and 1-3.
[0352] Table 1-1
[0353]
[0354] It should be noted that Examples 7, 8 and Comparative Example 6 contain acrylic resin instead of acrylic modified polyester resin, and Comparative Example 5 contains polyester resin instead of acrylic modified polyester resin. Therefore, in these Examples and Comparative Examples in the table, the acrylic modified polyester resin is replaced by acrylic resin and polyester resin, respectively.
[0355] Table 1-2
[0356]
[0357] Table 1-3
[0358]
[0359]
[0360] The number of layers in the table refers to the number of layers excluding the resin layer. In addition, since the resins A and B are the same, the laminated film 5 is a single-layer film. In addition, in Examples 1 to 28, only the composition of the resin composition is changed, so the obtained laminated films show the same characteristics as the laminated film 1 in Table 2.
[0361] (Examples 29 to 32, 34 to 40)
[0362] Laminated films (laminated films 2 to 5, 7, and 8) were prepared under the same conditions as in Example 1 except that the number of layers and resins of the multilayer films used in the laminated films were changed as described in Table 2. The resin layer properties of the obtained laminated films were the same as those of Example 1 shown in Tables 1-2 and 1-3. The evaluation results of the obtained laminated films are shown in Table 2. The evaluation results of laminated glass prepared using laminated films 2 to 5, 7, and 8 and having the structures described in Tables 3 and 4 are shown in Tables 3 and 4.
[0363] (Example 33)
[0364] A laminated film (laminated film 6) was produced under the same conditions as in Example 1 except that the heat treatment temperature of the laminated film was changed to 235°C and the width direction relaxation was changed to 1.3%. The resin layer properties of the obtained laminated film were the same as those of Example 1 shown in Tables 1-2 and 1-3. The evaluation results of the obtained laminated film are shown in Table 2. The evaluation results of the laminated glass using the laminated film 6 are shown in Table 3.
[0365] (Examples 41 to 44)
[0366] Table 4 shows the evaluation results of the glass laminates using the laminate film 7 and the laminate film 8.
[0367] (Example 45)
[0368] Resin 1 is used as a crystalline thermoplastic resin constituting layer A (hereinafter also referred to as resin A), and resin 2 is used as a thermoplastic resin constituting layer B (hereinafter also referred to as resin B). Resins A and B are melted at 280°C using different extruders, and foreign matter is removed through 5 FSS-type leaf disk filters. Then, while metering with a gear pump in a manner such that the discharge ratio becomes resin A / resin B=1 / 1.07, the two are merged using a 401-layer feed head, and resin A and resin B are alternately laminated 401 layers in the thickness direction in such a way that the outermost layers on both sides become resin A. At this time, the layer thickness of layer A and layer B is designed in such a way that the reflectivity spectrum in the wavelength range of 380nm to 1200nm becomes flat. Next, the obtained molten laminate is supplied to a T-die, and after being formed into a sheet, an electrostatic voltage of 8kV is applied by an electric wire, and it is quenched and solidified on a casting drum whose surface temperature is maintained at 25°C to obtain an unstretched film. The two sides were subjected to corona discharge treatment in air, and the resin composition was applied to the treated surface using a rod coater in a manner that the coating thickness was about 6 μm. Then, the two ends in the width direction were clamped with a clamp, and the uniaxially stretched film was introduced into a tenter, and after being transversely stretched at a temperature of 90°C and a magnification of 5.0 times, it was heat treated at 180°C and then relaxed in the width direction by 1.6%, to obtain a laminated film (laminated film 9) with a thickness of 80 μm. The obtained laminated film has polarized light reflectivity of reflecting 42% of P polarized light and 10% of S polarized light for visible light to infrared light with a wavelength of 380 to 1200 nm.
[0369] Table 2 shows the properties of the obtained laminated film 9 , and Table 4 shows the evaluation results of the laminated glass using the laminated film 9 .
[0370]
[0371]
[0372] Industrial Applicability
[0373] According to the present invention, a laminated film having excellent universal adhesion to various functional materials and high adhesion to various functional materials regardless of the temperature of use, especially even in a low temperature environment (below freezing point) can be provided. Since the laminated film of the present invention has excellent properties as described above, it can be applied to solar cell components, laminated glass, polarizer protective films, etc.
Claims
1. A laminated film having a resin layer on at least one surface, characterized in that: The resin layer satisfies at least one of the following characteristics A to C, when the normalized positive secondary ion intensity of each component at a position of 20% thickness and a position of 50% thickness from the surface layer of the resin layer by GCIB-TOF-SIMS is set to Xs and Xc, respectively, all components satisfy 0.5≤Xs / Xc≤2.0; Feature A: Contains three types of resins: acrylic resin, polyester resin and polyurethane resin; Feature B: Contains acrylic modified polyester resin and polyurethane resin; Feature C: Contains three skeletons: acrylic skeleton, polyester skeleton and polyurethane skeleton. 2 . The laminated film according to claim 1 , wherein the resin layer comprises a chemical structure derived from an oxazoline compound. The laminated film according to claim 1 or 2, wherein the resin layer contains an oxazoline compound. 4 . The laminate film according to claim 2 , wherein when the normalized positive secondary ion intensities of the oxazoline compound at the surface layer and at a position of 20% thickness of the resin layer by GCIB-TOF-SIMS are set to XO and XOs, respectively, XO / Xs≥1.0 is satisfied.
5. The laminated film according to any one of claims 1 to 4, wherein the AFM elastic modulus of the resin layer at a temperature of T°C is set as P(T), P(-20)-P(25) is set as ΔP, and P(-20) / P(25) is set as an elastic modulus ratio P', and the laminated film has at least one of the following features 1 and 2: Feature 1: The ΔP is greater than or equal to 0.2 GPa and less than or equal to 2.0 GPa; Feature 2: The elastic modulus ratio P' is greater than or equal to 0.1 and less than or equal to 2.
3. 6 . The laminated film according to claim 1 , wherein the resin layer has a glass transition temperature of 30° C. or higher and 80° C. or lower. 7 . The laminated film according to claim 1 , wherein a water droplet contact angle of the resin layer is 65° or more and 90° or less.
8. The laminated film according to any one of claims 1 to 7, wherein the resin layer has at least one structure of the following formulas (1) to (5): 9 . The laminated film according to claim 1 , wherein the resin layer contains a melamine compound.
10. The laminate film according to any one of claims 1 to 9, wherein when the normalized positive secondary ion intensity of each component at a position 80% of the thickness from the surface layer of the resin layer by GCIB-TOF-SIMS is set as Xb, all components satisfy 0.5≤Xb / Xc≤2.
0.
11. The laminated film according to any one of claims 1 to 10, comprising a laminated structure portion having more than 51 layers laminated thereon, wherein the laminated structure portion comprises at least an A layer and a B layer, wherein the A layer is a layer having a polyester resin, i.e., resin A, as a main component, and the B layer is a layer having a thermoplastic resin, i.e., resin B, which is different from the resin A, as a main component.
12. The laminate film according to any one of claims 1 to 11, having at least one reflection band with a continuous reflectivity of 30% or more over a wavelength width of 20 nm or more on at least one surface when light with a wavelength of 300 nm to 2500 nm is incident at an incident angle of 10°.
13. The laminate film according to any one of claims 1 to 12, wherein when light is incident on at least one surface at an incident angle of 10°, the average reflectivity in the wavelength range of 400nm to 700nm is 15% or less, and the average reflectivity in the wavelength range of 850nm to 1200nm is 70% or more.
14. According to any one of claims 1 to 12, the laminated film has an average transmittance of vertically incident visible light of more than 50% and less than 100% on at least one surface, and when the average reflectivity in % of P-wave with a wavelength of 400nm to 700nm is set to R20, R40, and R70 relative to the normal to the film surface at angles of 20°, 40°, and 70°, the relationship of R20≤R40<R70 is satisfied.
15. The laminate film according to any one of claims 1 to 14, wherein when the direction parallel to the film surface and in which the average rate of change of the heat shrinkage measured by thermomechanical analysis in the range of 100°C to 150°C is the largest is set as the X direction, the average rate of change of the heat shrinkage in the X direction is greater than or equal to 0.01% / °C and less than or equal to 0.1% / °C. 16 . A solar cell module having a structure in which the laminate film according to claim 1 and a sealing material are directly laminated. 17 . The solar cell module according to claim 16 , comprising two sealing materials (sealing materials 1 and 2 ), and including the sealing material 1 , a solar cell, the sealing material 2 , and the laminate film in this order. 18 . A glass structure comprising the laminate film according to claim 1 , an interlayer, and glass, wherein the laminate film is adjacent to the interlayer.
19. A glass structure comprising two glasses, namely glass 1 and glass 2, and two intermediate layers, namely intermediate layer 1 and intermediate layer 2, and comprising the glass 1, the intermediate layer 1, the laminated film according to any one of claims 1 to 15, the intermediate layer 2 and the glass 2 in this order. 20 . The glass structure according to claim 19 , wherein when the thickness of the intermediate layer 1 is d1 and the thickness of the intermediate layer 2 is d2 , 3≤d1 / d2≤100 is satisfied. 21 . The glass structure according to claim 19 , wherein when the thickness of the glass 1 is set to d3 and the thickness of the glass 2 is set to d4, 1.5≤d3 / d4≤10 is satisfied.
22. An automobile comprising the glass structure according to any one of claims 18 to 21.
23. A building material window comprising the glass structure according to any one of claims 18 to 21.
Citation Information
Patent Citations
Laminated polyester film
CN102762379A
Laminated film
CN105008131A
Pressure-sensitive adhesive label
JP1999296089A
Coated film
JP2004035761A
Easily adhesive sheet, protective sheet for solar cell, insulation sheet, back sheet member for sola cell, back sheet for solar cell and solar cell module
JP2014074149A
Cited By
Preparation method of high-frequency flexible copper-clad plate
CN121038113A
Preparation method of high frequency flexible copper clad laminate
CN121038113B
